Polycarbonate copolymer, coating liquid, electrophotographic photoreceptor, method for producing polycarbonate copolymer, and electric device

JP7644093B2Active Publication Date: 2025-03-11IDEMITSU KOSAN CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2022512700
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-01
Filing Date
2021-04-01
Publication Date
2025-03-11
Estimated Expiration
2041-04-01

Smart Images

  • Figure 0007644093000001
    Figure 0007644093000001
  • Figure 0007644093000002
    Figure 0007644093000002
  • Figure 0007644093000003
    Figure 0007644093000003
Patent Text Reader

Abstract

A polycarbonate copolymer having repeating units A represented by formula (1) and repeating units B represented by formula (2), the polycarbonate copolymer being obtained using bis-chloroformate oligomers represented by formula (1A) and / or formula (2A) as a raw material, and being such that the average polymer number n1 of bis-chloroformate oligomers represented by formula (1A) is 1.0-1.3 (inclusive), and the average polymer number n2 of bis-chloroformate oligomers represented by formula (2A) is 1.0-1.3 (inclusive). In formula (1), Ar1 is a group represented by formula (3). In formula (2), Ar2 is a group represented by formula (4). In formula (1A), Ar1 is synonymous with Ar1 in formula (1). In formula (2A), Ar2 is synonymous with Ar2 in formula (2). n1 and n2 represent the average polymer number.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polycarbonate copolymer, a coating liquid, an electrophotographic photoreceptor, a method for producing the polycarbonate copolymer, and an electric device. [Background technology]

[0002] Polycarbonate resins have excellent mechanical, thermal, and electrical properties. Therefore, polycarbonate resins have been used as materials for molded products and the like in various industrial fields. In recent years, polycarbonate resins have been widely used in the field of functional products by utilizing the optical properties and the like of polycarbonate resins in addition to the above-mentioned properties. With the expansion of such applications and fields, the performance required for polycarbonate resins has also become more diverse. Such demands on polycarbonate resins may not be met adequately by polycarbonate resins obtained by simply polycondensing conventional raw materials (e.g., 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, etc.) Therefore, polycarbonate copolymers having various chemical structures have been proposed according to the applications and required properties.

[0003] Incidentally, an example of a product that utilizes the electrical and optical properties of polycarbonate resin is an electrophotographic photoreceptor that uses polycarbonate resin as a binder resin for functional materials such as a charge generating material and a charge transporting material.

[0004] An electrophotographic photoreceptor is required to have predetermined sensitivity, electrical characteristics and optical characteristics according to the electrophotographic process. In addition, since various operations (e.g., corona charging, toner development, transfer onto paper, cleaning treatment, etc.) are repeatedly performed on the surface of the photosensitive layer of the electrophotographic photoreceptor, at least one of an electrical external force and a mechanical external force is applied each time the operation is performed. Therefore, in order to maintain the image quality of electrophotography over a long period of time, the photosensitive layer provided on the surface of the electrophotographic photoreceptor is required to have durability against these external forces.

[0005] In recent years, with the introduction of various printer systems, it is known that wear of electrophotographic photoconductors occurs due to various factors (wear modes). Known wear of electrophotographic photoconductors includes mechanical wear (for example, fatigue wear and abrasive wear) and electrical wear caused by discharge deterioration due to a charging roller, etc. Therefore, there is a demand for a binder resin that is effective against the wear that occurs in the above-mentioned wear mode.

[0006] Conventionally, polycarbonate resins made from 2,2-bis(4-hydroxyphenyl)propane or 2,2-bis(4-hydroxyphenyl)cyclohexane have been used as binder resins for photoreceptors, but they are not sufficient in terms of durability. Therefore, various methods have been used to meet the demand for high durability of binder resins for photoreceptors. Copolymerized polycarbonates are known as an effective technology for improving the wear resistance of the photosensitive layer of an electrophotographic photoreceptor.

[0007] For example, Patent Document 1 describes a polycarbonate copolymer obtained by polycondensation of a biphenol having a rigid skeleton and a bischloroformate oligomer derived from a dihydric phenol compound having a monomer number of about 2mer to 4mer, and describes that the copolymerization ratio of the biphenol component in the polycarbonate copolymer is about 25 mol%.

[0008] Patent Documents 2 and 3 disclose polycarbonate copolymers obtained by polycondensing a bischloroformate oligomer derived from a dihydric phenol compound having a monomer number to a dimer number and a dihydric phenol compound containing biphenol, etc. It is disclosed that the copolymerization ratio of biphenol, etc. in the polycarbonate copolymer is nearly 50 mol %.

[0009] Furthermore, Patent Document 4 describes an electrophotographic photoreceptor containing a specific charge generating material and a specific polycarbonate resin in a photosensitive layer, and describes that the specific polycarbonate resin is a polycarbonate copolymer having a repeating unit containing a terphenyl skeleton or an anthracene skeleton, which is more rigid than biphenol, and a repeating unit containing a bisphenol skeleton.

[0010] Furthermore, Patent Document 5 describes an electrophotographic photoreceptor having, in this order, a support, a charge generation layer containing a specific charge generation substance, and a charge transport layer containing a specific polycarbonate, and describes that the specific polycarbonate has a structural unit containing a m-terphenyl skeleton. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] Japanese Patent Application Publication No. 4-179961 [Patent Document 2] JP 2011-26574 A [Patent Document 3] JP 2011-26575 A [Patent Document 4] Japanese Patent Application Publication No. 9-43882 [Patent Document 5] JP 2017-76126 A Summary of the Invention [Problem to be solved by the invention]

[0012] The polycarbonate copolymer described in Patent Document 1 is produced by copolymerizing a bisphenol Z skeleton having good solubility with biphenol having good abrasion resistance. The polycarbonate copolymer is produced using a raw material having an oligomer number of about dimer to tetramer. Therefore, the copolymerization ratio of the biphenol component in the polycarbonate copolymer is limited to about 23 mol%, and the abrasion resistance is insufficient.

[0013] The polycarbonate copolymers described in Patent Documents 2 and 3 are produced from raw materials with a reduced number of oligomers. Therefore, the copolymerization ratio of the skeleton of biphenol or the like in the polycarbonate copolymer is improved to 25 mol% to 47 mol%. However, even the polycarbonate copolymers described in Patent Documents 2 and 3 do not have sufficient wear resistance to meet the need for high durability against mechanical deterioration (e.g., abrasive wear) that occurs when a toner containing a large amount of external additives is used.

[0014] The polycarbonate copolymers described in Patent Documents 4 and 5 contain a m-terphenyl skeleton, which is a skeleton such as terphenyl that is more rigid than biphenol, etc., and is expected to improve durability against abrasive wear. However, the structure and composition of these polycarbonate copolymers are not optimized for applications requiring wear resistance, and the wear resistance is insufficient. Furthermore, when the polycarbonate copolymer is used by dissolving it in an organic solvent, the polycarbonate copolymer is required to have good solubility in the organic solvent.

[0015] An object of the present invention is to provide a polycarbonate copolymer having excellent abrasion resistance and good solubility in organic solvents, a method for producing the polycarbonate copolymer, a coating liquid using the polycarbonate copolymer, an electrophotographic photoreceptor using the polycarbonate copolymer, and an electrical device using the electrophotographic photoreceptor. [Means for solving the problem]

[0016] The polycarbonate copolymer according to one embodiment of the present invention has a repeating unit A represented by the following general formula (1) and a repeating unit B represented by the following general formula (2), and is obtained from at least one of a bischloroformate oligomer represented by the following general formula (1A) and a bischloroformate oligomer represented by the following general formula (2A), The average number of monomers n1 of the bischloroformate oligomer represented by the general formula (1A) is 1.0 or more and 1.3 or less, The average number of monomers n2 of the bischloroformate oligomer represented by the general formula (2A) is 1.0 or more and 1.3 or less.

[0017] [ka]

[0018] (In the above general formula (1), Ar 1 is a group represented by the following general formula (3): In the general formula (2), Ar 2 is a group represented by the following general formula (4):

[0019] [ka]

[0020] [In the general formulas (3) and (4), R 11 ~R 18 and R 21 ~R 28 are each independently a hydrogen atom or a substituent, R as a Substituent 11 ~R 18 and R 21 ~R 28 are each independently an unsubstituted alkyl group having 1 to 2 carbon atoms; an unsubstituted fluoroalkyl group having 1 to 2 carbon atoms; an unsubstituted alkoxy group having 1 to 2 carbon atoms, X 1 teeth, -CR 3 R 4 A group represented by -, a substituted or unsubstituted cycloalkylidene group having 5 to 6 carbon atoms; a substituted or unsubstituted bicyclohydrocarbon diyl group having 7 to 10 carbon atoms, or a substituted or unsubstituted tricyclohydrocarbon diyl group having 10 to 16 carbon atoms, R 3 and R 4 are each independently a hydrogen atom or a substituent, R as a Substituent 3 and R 4 are each independently an unsubstituted alkyl group having 1 to 3 carbon atoms; an unsubstituted fluoroalkyl group having 1 to 3 carbon atoms, or It is a substituted or unsubstituted aryl group having 6 to 12 ring carbon atoms.]

[0021] [ka]

[0022] [In the above general formula (1A), Ar 1 is a group represented by the general formula (3), n1 represents the average number of monomers, In the general formula (2A), Ar 2 is a group represented by the general formula (4), and n2 represents the average number of monomers.

[0023] In a method for producing a polycarbonate copolymer according to one embodiment of the present invention, a polycarbonate copolymer is produced by the following synthesis reaction (CS1), (CS2) or (CS3). (CS1) A bischloroformate oligomer represented by the following general formula (1A) and a dihydric phenolic compound represented by the following general formula (6) are subjected to interfacial polycondensation in the presence of an acid binder. (CS2) A bischloroformate oligomer represented by the following general formula (2A) and a dihydric phenolic compound represented by the following general formula (5) are subjected to interfacial polycondensation in the presence of an acid binder. (CS3) A bischloroformate oligomer represented by the following general formula (1A) is mixed with a bischloroformate oligomer represented by the following general formula (2A), and the mixture of the bischloroformate oligomer represented by the following general formula (1A) and the bischloroformate oligomer represented by the following general formula (2A) is subjected to interfacial polycondensation with a dihydric phenolic compound represented by the following general formula (5) or a dihydric phenolic compound represented by the following general formula (6).

[0024] [ka]

[0025] [In the above general formulae (1A) and (5), Ar 1 is a group represented by the following general formula (3), and in the general formulas (2A) and (6), Ar 2 is a group represented by the following general formula (4): In the general formula (1A), n1 represents the average number of monomers and is 1.0 or more and 1.3 or less. In the general formula (2A), n2 represents the average number of monomers and is 1.0 or more and 1.3 or less. [ka]

[0026] [In the general formulas (3) and (4), R 11 ~R 18 and R 21 ~R 28 are each independently a hydrogen atom or a substituent, R as a Substituent 11 ~R 18 and R 21 ~R 28 are each independently an unsubstituted alkyl group having 1 to 2 carbon atoms; an unsubstituted fluoroalkyl group having 1 to 2 carbon atoms; an unsubstituted alkoxy group having 1 to 2 carbon atoms, X 1 teeth, -CR 3 R 4 A group represented by -, a substituted or unsubstituted cycloalkylidene group having 5 to 6 carbon atoms; a substituted or unsubstituted bicyclohydrocarbon diyl group having 7 to 10 carbon atoms, or a substituted or unsubstituted tricyclohydrocarbon diyl group having 10 to 16 carbon atoms, R 3 and R 4 are each independently a hydrogen atom or a substituent, R as a Substituent 3 and R 4 are each independently an unsubstituted alkyl group having 1 to 3 carbon atoms; an unsubstituted fluoroalkyl group having 1 to 3 carbon atoms, or It is a substituted or unsubstituted aryl group having 6 to 12 ring carbon atoms.]

[0027] The coating fluid according to one embodiment of the present invention contains the polycarbonate copolymer according to one embodiment of the present invention and an organic solvent. An electrophotographic photoreceptor according to an embodiment of the present invention contains the polycarbonate copolymer according to an embodiment of the present invention. An electrophotographic photoreceptor according to one aspect of the present invention includes a substrate and a photosensitive layer provided on the substrate, the photosensitive layer including the polycarbonate copolymer according to one aspect of the present invention. An electrical device according to an aspect of the present invention includes the electrophotographic photoreceptor according to an aspect of the present invention.

[0028] According to the present invention, it is possible to provide a polycarbonate copolymer having excellent abrasion resistance and good solubility in organic solvents, a method for producing the polycarbonate copolymer, a coating liquid using the polycarbonate copolymer, an electrophotographic photoreceptor using the polycarbonate copolymer, and an electrical device using the electrophotographic photoreceptor. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] As a result of extensive research, the present inventors have found that a polycarbonate copolymer excellent in wear resistance (particularly abrasive wear resistance) can be obtained by using at least one of a bischloroformate oligomer having an m-terphenyl skeleton (bischloroformate oligomer derived from a repeating unit A represented by general formula (1)) and a bischloroformate oligomer having a bisphenol skeleton (bischloroformate oligomer derived from a repeating unit B represented by general formula (2)) as a raw material, thereby completing the present invention. Note that the bischloroformate oligomer having an m-terphenyl skeleton and the bischloroformate oligomer having a bisphenol skeleton both have an average number of monomers adjusted to be 1.0 or more and 1.3 or less, which is a low number of monomers. The inventors have also determined that excellent wear resistance is related to good breaking strain. Furthermore, the present inventors have found that by using at least one of a bischloroformate oligomer having a m-terphenyl skeleton and a bischloroformate oligomer having a bisphenol skeleton as a raw material, it is possible to obtain a polycarbonate copolymer that has good solubility in organic solvents, can suppress crystallization, and can suppress clouding of the solution due to crystallization, even when the copolymer contains a relatively high proportion of a highly crystalline and rigid m-terphenyl skeleton.

[0030] Example 10 of Patent Document 2 (JP 2011-26574 A) describes a polycarbonate copolymer obtained by reacting a low-mer bischloroformate oligomer having a divalent aromatic group of bisphenol Z with a biphenol monomer. The polycarbonate copolymer of the present embodiment has better wear resistance (particularly abrasive wear resistance) and better wear-related breaking strain than the polycarbonate copolymer described in Patent Document 2 (JP 2011-26574 A). In addition, as described above, even if the polycarbonate copolymer of the present embodiment contains a relatively high proportion of the highly crystalline and rigid m-terphenyl skeleton, it has good solubility in an organic solvent, can suppress crystallization, and can suppress the clouding of the solution due to crystallization. Therefore, the polycarbonate copolymer of the present embodiment has good abrasion resistance even when used for an electrophotographic photoreceptor, and an electrophotographic photoreceptor using the polycarbonate copolymer can exhibit good electrophotographic characteristics.

[0031] Hereinafter, a polycarbonate copolymer according to one embodiment of the present invention (hereinafter, the polycarbonate copolymer may be simply referred to as a "PC copolymer"), a coating liquid using the PC copolymer, an electrophotographic photoreceptor using the PC copolymer, and an electrical device using the electrophotographic photoreceptor will be described in detail. In this specification, a numerical range expressed using "to" means a range that includes the numerical value before "to" as the lower limit and the numerical value after "to" as the upper limit.

[0032] [PC copolymer structure] The PC copolymer of the present embodiment has a repeating unit A represented by the following general formula (1) and a repeating unit B represented by the following general formula (2), and is obtained using at least one of a bischloroformate oligomer represented by the following general formula (1A) and a bischloroformate oligomer represented by the following general formula (2A) as a raw material. The average number of monomers n1 of the bischloroformate oligomer represented by the general formula (1A) is 1.0 or more and 1.3 or less. The average number of monomers n2 of the bischloroformate oligomer represented by the general formula (2A) is 1.0 or more and 1.3 or less.

[0033] [ka]

[0034] (In the above general formula (1), Ar 1 is a group represented by the following general formula (3), and in the general formula (2), Ar2 is a group represented by the following general formula (4). * indicates the bonding position.

[0035] [ka]

[0036] [In the general formulas (3) and (4), R 11 ~R 18 and R 21 ~R 28 are each independently a hydrogen atom or a substituent, R as a Substituent 11 ~R 18 and R 21 ~R 28 are each independently an unsubstituted alkyl group having 1 to 2 carbon atoms; an unsubstituted fluoroalkyl group having 1 to 2 carbon atoms; an unsubstituted alkoxy group having 1 to 2 carbon atoms, X 1 teeth, -CR 3 R 4 A group represented by -, a substituted or unsubstituted cycloalkylidene group having 5 to 6 carbon atoms; a substituted or unsubstituted bicyclohydrocarbon diyl group having 7 to 10 carbon atoms, or a substituted or unsubstituted tricyclohydrocarbon diyl group having 10 to 16 carbon atoms, R 3 and R 4 are each independently a hydrogen atom or a substituent, R as a Substituent 3 and R 4 are each independently an unsubstituted alkyl group having 1 to 3 carbon atoms; an unsubstituted fluoroalkyl group having 1 to 3 carbon atoms, or A substituted or unsubstituted aryl group having 6 to 12 ring carbon atoms. * indicates the bonding position.]

[0037] [ka]

[0038] [In the above general formula (1A), Ar 1 is a group represented by the general formula (3), n1 represents the average number of monomers, In the general formula (2A), Ar 2 is a group represented by the general formula (4), and n2 represents the average number of monomers.

[0039] In this specification, hydrogen atoms include isotopes having different numbers of neutrons, namely protium, deuterium, and tritium.

[0040] In the general formulas (3) and (4), R 11 ~R 18 and R 21 ~R 28 Examples of the alkyl group having 1 to 2 carbon atoms constituting the formula include a methyl group and an ethyl group, and a methyl group is preferred. In the general formulas (3) and (4), R 11 ~R 18 and R 21 ~R 28 The fluoroalkyl group having 1 to 2 carbon atoms constituting the formula (1) includes the above-mentioned alkyl group having 1 to 2 carbon atoms substituted with one or more fluorine atoms. Preferred is a perfluoroalkyl group, for example, a trifluoromethyl group. In the general formulas (3) and (4), R 11 ~R 18 and R 21 ~R 28 Examples of the alkoxy group having 1 to 2 carbon atoms constituting the formula include a methoxy group and an ethoxy group.

[0041] In the general formulas (3) and (4), R 3 and R 4The alkyl group having 1 to 3 carbon atoms constituting the alkyl group includes a straight chain alkyl group or a branched alkyl group. For example, the alkyl group includes a methyl group, an ethyl group, and various propyl groups. The methyl group is preferable. In the general formulas (3) and (4), R 3 and R 4 Examples of the fluoroalkyl group having 1 to 3 carbon atoms constituting the above include the above alkyl group having 1 to 3 carbon atoms substituted with one or more fluorine atoms. Preferred are perfluoroalkyl groups, such as a trifluoromethyl group. In the general formulas (3) and (4), R 3 and R 4 Examples of the aryl group having 6 to 12 ring carbon atoms include a phenyl group, a biphenyl group, and a naphthyl group.

[0042] In the general formulas (3) and (4), X 1 Examples of the cycloalkylidene group having 5 to 6 carbon atoms constituting the formula (1) include a cyclopentylidene group, a cyclohexylidene group, and a 3,5,5-trimethylcyclohexylidene group.

[0043] The bicyclohydrocarbon diyl group refers to a divalent group derived by removing two hydrogen atoms from a bicyclohydrocarbon. In the general formulas (3) and (4), X 1 Examples of the bicyclohydrocarbon diyl group having 7 to 10 carbon atoms constituting the formula (1) include divalent groups derived from any of decahydronaphthalene (bicyclo[4.4.0]decane), norbornane (bicyclo[2.2.1]heptane), bornane, bicyclo[4.2.0]octane, bicyclo[4.3.0]nonane, bicyclo[3.3.1]nonane, and perhydroazulene.

[0044] The tricyclohydrocarbon diyl group refers to a divalent group derived by removing two hydrogen atoms from a tricyclohydrocarbon. In the general formulas (3) and (4), X 1Examples of the tricyclohydrocarbon diyl group having 10 to 16 carbon atoms constituting the above-mentioned compound include perhydroanthracene, 10,10-dimethyl-2,3,4,4a,5,6,7,8,8a,9,9a,10a-dodecahydro-1H-anthracene, perhydrofluorene, tricyclo[8.5.0.0 2,8 ]pentadecane, exo-tricyclo[5.5.5.0 2,6 ]decane, and endo-tricyclo[5.5.5.0 2,6 ]decane, and the like.

[0045] In the present specification, examples of the substituent in the case of "substituted or unsubstituted" include at least one group selected from the group consisting of aryl groups having 6 to 12 ring carbon atoms (e.g., phenyl, biphenyl, naphthyl, etc.), heteroaryl groups having 5 to 12 ring atoms (e.g., pyridyl, etc.), alkyl groups having 1 to 20 carbon atoms (e.g., methyl, ethyl, n-propyl, isopropyl, etc.), fluoroalkyl groups having 1 to 20 carbon atoms (e.g., fluoromethyl and difluoromethyl groups), alkoxy groups having 1 to 20 carbon atoms (e.g., methoxy and ethoxy groups), and halogen atoms. Examples of halogen atoms include fluorine atoms, chlorine atoms, and bromine atoms. In this specification, the substituent in the case of "substituted or unsubstituted" may be further substituted with at least one group selected from the group consisting of an aryl group having 6 to 12 ring carbon atoms, a heteroaryl group having 5 to 12 ring atoms, an alkyl group having 1 to 20 carbon atoms, a fluoroalkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, and a halogen atom.

[0046] In the PC copolymer of this embodiment, Ar 1 / (Ar 1 +Ar 2 The abundance ratio represented by (a) is preferably 30 mol % or more and 55 mol % or less, more preferably 35 mol % or more and 45 mol % or less, and further preferably 38 mol % or more and 43 mol % or less. Ar 1 / (Ar1 +Ar 2 When the abundance ratio represented by (x) is 30 mol % or more, the effect of improving the abrasion resistance is easily achieved. Ar 1 / (Ar 1 +Ar 2 ) is 55 mol % or less, crystallization of the highly regular m-terphenyl structure is unlikely to occur, and a decrease in solubility in organic solvents is suppressed. The above "mol %" refers to the molar copolymer composition expressed as a percentage. The molar copolymer composition can be measured from a nuclear magnetic resonance spectrum, and specifically, can be determined by the method described in the Examples.

[0047] In the PC copolymer of this embodiment, Ar 2 / (Ar 1 +Ar 2 The abundance ratio represented by (a) is preferably 45 mol % or more and 70 mol % or less, more preferably 55 mol % or more and 65 mol % or less, and further preferably 57 mol % or more and 62 mol % or less. Ar 2 / (Ar 1 +Ar 2 ) is 45 mol % or more, crystallization of the highly regular m-terphenyl structure is unlikely to occur, and a decrease in solubility in organic solvents is suppressed. Ar 2 / (Ar 1 +Ar 2 When the abundance ratio represented by (x, y) is 70 mol % or less, the effect of improving the abrasion resistance is easily achieved.

[0048] In the PC copolymer of the present embodiment, in the general formula (4), X 1 -CR 3 R 4 -, or a substituted or unsubstituted cycloalkylidene group having 5 to 6 carbon atoms. X 1 -CR 3 R 4 -, R3 and R 4 is preferably each independently an unsubstituted alkyl group having 1 to 3 carbon atoms.

[0049] In the PC copolymer of this embodiment, R 11 ~R 18 and R 21 ~R 28 are preferably each independently a hydrogen atom or an unsubstituted alkyl group having 1 to 2 carbon atoms.

[0050] In the PC copolymer of this embodiment, R 11 and R 16 are preferably the same. In the PC copolymer of this embodiment, R 12 and R 15 are preferably the same. In the PC copolymer of this embodiment, R 13 and R 18 are preferably the same. In the PC copolymer of this embodiment, R 14 and R 17 are preferably the same.

[0051] In the PC copolymer of this embodiment, R 21 and R 26 are preferably the same. In the PC copolymer of this embodiment, R 22 and R 25 are preferably the same. In the PC copolymer of this embodiment, R 23 and R 28 are preferably the same. In the PC copolymer of this embodiment, R 24 and R 27 are preferably the same. In the PC copolymer of this embodiment, R 3 and R 4 are preferably different from each other.

[0052] The PC copolymer having the repeating unit A represented by the general formula (1) and the repeating unit B represented by the general formula (2) is preferably one represented by the following general formula (100).

[0053] [ka]

[0054] In the general formula (100), a represents the molar copolymerization ratio in the repeating unit A, and b represents the molar copolymerization ratio in the repeating unit B. a is Ar 1 / (Ar 1 +Ar 2 ), b is Ar 2 / (Ar 1 +Ar 2 ). Ar as abundance ratio 1 / (Ar 1 +Ar 2 ) is Ar 1 is expressed as a mole percentage. Ar as molar copolymerization ratio 1 / (Ar 1 +Ar 2 ) is Ar 1 It is expressed as a mole fraction of Ar 2 The same applies to the abundance ratio and molar copolymerization ratio of the above.

[0055] In the general formula (100), the repeating units are not necessarily consecutive. The PC copolymer represented by the general formula (100) may be any of a block copolymer, an alternating copolymer, a random copolymer, and the like.

[0056] In the PC copolymer of this embodiment, Ar 1 Examples of the group include groups represented by the following general formulae (3-1) to (3-4), in which * indicates the bonding position.

[0057] [ka]

[0058] In the PC copolymer of the present embodiment, in the general formula (2), Ar 2 is preferably a group represented by the following general formula (4A) or (4B).

[0059] [ka]

[0060] (In the general formulas (4A) and (4B), R 21 ~R 28 each independently represents R in the general formula (4). 21 ~R 28 * indicates the bond position.)

[0061] In the PC copolymer of the present embodiment, in the general formula (2), Ar 2 is more preferably a group represented by the following general formula (4A).

[0062] [ka]

[0063] (In the general formula (4A), R 21 ~R 28 each independently represents R in the general formula (4). 21 ~R 28 * indicates the bond position.)

[0064] In the PC copolymer of the present embodiment, in the general formula (1), Ar 1 is a divalent group derived from 4,4″-dihydroxy-m-terphenyl, and in the general formula (2), Ar 2 is more preferably a group represented by the general formula (4A).

[0065] In the PC copolymer of this embodiment, Ar 2 Examples of the group include groups represented by the following general formulae (4-1) to (4-6), in which * indicates the bonding position.

[0066] [ka]

[0067] The PC copolymer of the present embodiment is obtained by using, as a raw material, at least one of a bischloroformate oligomer represented by the general formula (1A) having an average number of monomers n1 in the range of 1.0 to 1.3 and a bischloroformate oligomer represented by the general formula (2A) having an average number of monomers n2 in the range of 1.0 to 1.3, and a highly crystalline Ar 1 Even when the PC copolymer has a polysaccharide skeleton, the triad fraction of AAA triads (structural units AAA consisting of three consecutive repeating units A) in the PC copolymer can be suppressed to 5 mol % or less. As a result, crystallization of the PC copolymer can be suppressed, resulting in a PC copolymer with good solubility in organic solvents.

[0068] Here, we will explain triplets and triplet fractions. In the PC copolymer of the present embodiment, structural units ABA, BAA, AAA, AAB, BBA, BAB, ABB, and BBB each constituted by three consecutive repeating units A represented by general formula (1) or three consecutive repeating units B represented by general formula (2) are defined as a triad. The number of moles of each triad relative to the total number of moles of all triads (ABA, BAA, AAA, AAB, BBA, BAB, ABB, and BBB) expressed as a percentage is defined as the triad fraction. For example, in the chain of repeating units A and B shown below, in addition to ABA and BAA shown in a square, there are a total of eight triads represented by AAA, AAB, BBA, BAB, ABB, and BBB. In this chain, the number of moles of each triad out of the total number of moles of the eight triads expressed as a percentage is the triad fraction.

[0069] Diads and diad fractions can be explained in the same way as triads and triad fractions. In the PC copolymer of the present embodiment, the structural units AA, BB, AB, and BA each composed of two consecutive repeating units A represented by the general formula (1) or two consecutive repeating units B represented by the general formula (2) are defined as a diad. The number of moles of each diad relative to the total number of moles of all diads (AA, BB, AB, and BA) is defined as the diad fraction, expressed as a percentage. For example, in the chain of repeating units A and B shown below, in addition to AA and BB enclosed in ellipses, there are a total of four diads represented by AB and BA. In this chain, the diad fraction is the percentage of the number of moles of each diad out of the total number of moles of the four diads.

[0070] [ka]

[0071] When the PC copolymer of the present embodiment has, for example, a repeating unit A and a repeating unit B represented by the following general formula, 13 In the C-NMR spectrum, the carbon at the 4th position, indicated by α, β, γ, and δ in the following general formula, shows a unique shift value due to the influence of the left and right skeletons. In the case of the following general formula, it is influenced by the left and right A skeletons. This allows us to know the percentage of each of the triplet patterns represented by ABA, BAA, AAA, AAB, BBA, BAB, ABB, and BBB. 13 The C-NMR spectrum is measured, for example, under the following measurement conditions.

[0072] ( 13 C-NMR spectrum measurement conditions) Equipment: Bruker Japan Co., Ltd. (AVANCE III HD 500) (5mmφ TCI cryoprobe used) Solvent: CD2Cl2 Measurement concentration (sample volume / solvent volume): 50mg / mL -Number of times of accumulation: 1024 times (about 1 hour)

[0073] [ka]

[0074] In the PC copolymer of this embodiment, when the structural units ABA, BAA, AAA, AAB, BBA, BAB, ABB, and BBB each constituted by three consecutive repeating units A represented by general formula (1) or three consecutive repeating units B represented by general formula (2) are defined as a triad, the percentage of the number of moles of triads represented by AAA to the total number of moles of a total of eight types of triads represented by ABA, BAA, AAA, AAB, BBA, BAB, ABB, and BBB (triad fraction) is preferably 3 mol % or less, more preferably 2 mol % or less, and even more preferably 1 mol % or less. When the percentage of the number of moles of the triads represented by AAA (triad fraction) is 3 mol % or less, the crystallinity of the resin decreases and the solubility in organic solvents increases, which results in improved compatibility with charge transport materials and the like, and improved wear resistance and electrical properties of the photoreceptor.

[0075] In the PC copolymer of the present embodiment, when the structural units AA, BB, AB, and BA each consisting of two consecutive repeating units A represented by the general formula (1) or two consecutive repeating units B represented by the general formula (2) are defined as a diad, the percentage of the number of moles of diads represented by AA to the total number of moles of the four types of diads represented by AA, BB, AB, and BA (diad fraction) is preferably 5 mol % or less, more preferably 3 mol % or less, and even more preferably 1 mol % or less. When the percentage of the number of moles of diads represented by AA (diad fraction) is 5 mol % or less, the crystallinity of the resin decreases and the solubility in organic solvents increases, which results in improved compatibility with charge transport materials and the like, and improved wear resistance and electrical properties of the photoreceptor.

[0076] It is preferable that the PC copolymer of the present embodiment dissolves in THF (tetrahydrofuran) at a solid content concentration of 10 mass %, and the haze value of the solution is 3% or less. The haze value is more preferably 2% or less, and further preferably 1% or less. When the haze value is 3% or less, a PC copolymer having excellent transparency can be obtained. The haze value can be measured by the method described in the Examples below.

[0077] The PC copolymer of this embodiment preferably has a breaking strain of 65% or more at a tensile speed of 1 mm / min in a tensile test. The breaking strain is more preferably 70% or more, and further preferably 75% or more. When the breaking strain is 65% or more, the PC copolymer obtained has improved abrasion resistance. The breaking strain can be measured by the method described in the Examples below.

[0078] A film sample is obtained by dissolving 2 g of the PC copolymer of this embodiment in methylene chloride and casting it onto a PET film. The cast surface of the film sample is then contacted with a Taber abrasion wheel (model number: CS-10) carrying a load of 500 g and rotated 700 times, after which the mass loss of the film sample is preferably 3.0 mg or less. The mass loss is more preferably 2.5 mg or less, and further preferably 2.0 mg or less. When the mass loss is 3.0 mg or less, the PC copolymer obtained has improved abrasion resistance. The mass loss can be measured by the method described in the Examples below.

[0079] In this embodiment, the reduced viscosity [η SP / C] is the value of a methylene chloride solution of PC copolymer with a concentration of 0.5 g / dL at 20°C. The reduced viscosity [η SP / C] is preferably 0.1 dL / g or more and 5 dL / g or less, more preferably 0.2 dL / g or more and 3 dL / g or less, and even more preferably 0.3 dL / g or more and 2.5 dL / g or less. Reduced viscosity of PC copolymer [η SP When the molecular weight ratio of the binder resin to the polymerizable composition is 0.1 dL / g or more, sufficient abrasion resistance can be obtained when the binder resin is used as an electrophotographic photoreceptor or the like. Reduced viscosity of PC copolymer [η SP When the viscosity of the coating liquid is 5 dL / g or less, the coating viscosity can be kept appropriate when a molded body such as an electrophotographic photoreceptor is produced from the coating liquid, and the productivity of the molded body such as an electrophotographic photoreceptor can be increased. The reduced viscosity can be measured by the method described in the Examples below.

[0080] In terms of improving electrical properties, the PC copolymer of this embodiment is preferably one in which the chain ends are blocked with a monovalent aromatic group or a monovalent fluorine-containing aliphatic group. The monovalent aromatic group may be a group that contains an aliphatic group, such as an alkyl group. The monovalent fluorine-containing aliphatic group may be a group containing an aromatic group. In addition, the monovalent aromatic group and the monovalent fluorine-containing aliphatic group may have a substituent such as an alkyl group, a halogen atom, and an aryl group added thereto. These substituents may have a further substituent such as an alkyl group, a halogen atom, and an aryl group added thereto. In addition, when there are a plurality of substituents, these substituents may be bonded to each other to form a ring.

[0081] The monovalent aromatic group constituting the chain end preferably contains an aryl group having a carbon number of 6 to 12. Examples of such aryl groups include a phenyl group and a biphenyl group. Examples of the substituent added to the aromatic group and the substituent added to the alkyl group added to the aromatic group include halogen atoms such as fluorine atom, chlorine atom, and bromine atom. Examples of the substituent added to the aromatic group include alkyl groups having 1 to 20 carbon atoms. The alkyl group may be a group to which a halogen atom is added as described above, or may be a group to which an aryl group is added.

[0082] Examples of the monovalent fluorine-containing aliphatic group constituting the chain end include monovalent groups derived from fluorine-containing alcohols.

[0083] The fluorine-containing alcohol is preferably a fluorine-containing alcohol in which a plurality of fluoroalkyl chains having 2 to 6 carbon atoms are linked together via ether bonds and in which the total number of fluorine atoms is 13 to 19. If the total number of fluorine atoms is 13 or more, sufficient water repellency and oil repellency can be exhibited. On the other hand, if the total number of fluorine atoms is 19 or less, a decrease in reactivity during polymerization can be suppressed, and the mechanical strength, surface hardness, heat resistance, etc. of the obtained PC copolymer can be improved. Furthermore, the monovalent fluorine-containing aliphatic group is preferably a monovalent group derived from a fluorine-containing alcohol having two or more ether bonds. By using such a fluorine-containing alcohol, the dispersibility of the PC copolymer in the coating liquid is improved, the wear resistance of the molded body and the electrophotographic photoreceptor is improved, and the surface lubricity, water repellency, and oil repellency after wear can be maintained.

[0084] Alternatively, the fluorine-containing alcohol is preferably a fluorine-containing alcohol represented by the following general formula (30) or (31), a fluorine-containing alcohol such as 1,1,1,3,3,3-hexafluoro-2-propanol, or a fluorine-containing alcohol having an ether bond represented by the following general formula (32), (33), or (34).

[0085] H(CF2) n1 CH2OH···(30) F(CF2) m1 CH2OH···(31)

[0086] In the general formula (30), n1 is an integer from 1 to 12, and in the general formula (31), m1 is an integer from 1 to 12.

[0087] F-(CF2) n 31 -OCF2CH2-OH···(32) F-(CF2CF2) n 32 -(CF2CF2O) n 33 -CF2CH2OH···(33) C(R)3-(CF2) n 35 -O-(CF2CF2O) n 34 -CF2CH2OH···(34)

[0088] In the general formula (32), n 31 is an integer from 1 to 10, and preferably an integer from 5 to 8. In the general formula (33), n 32 is an integer of 0 to 5, and preferably an integer of 0 to 3. 33 is an integer of 1 to 5, and preferably an integer of 1 to 3. In the general formula (34), n 34 is an integer of 1 to 5, and preferably an integer of 1 to 3. 35 is an integer of 0 to 5, and preferably an integer of 0 to 3. R is CF3 or F.

[0089] In this embodiment, from the viewpoint of improving the electrical properties and abrasion resistance, it is preferable that the chain ends of the PC copolymer are blocked with a monovalent group derived from a phenol represented by the following general formula (9) or a monovalent group derived from a fluorine-containing alcohol represented by the following general formula (10).

[0090] [ka]

[0091] In the general formula (9), R 10 represents an alkyl group having 1 to 10 carbon atoms or a fluoroalkyl group having 1 to 10 carbon atoms; and p is an integer of 1 to 3. In the general formula (10), R f represents a perfluoroalkyl group having 5 or more carbon atoms and 11 or more fluorine atoms, or a perfluoroalkyloxy group represented by the following general formula (11).

[0092] [ka]

[0093] In the general formula (11), R f2 is a straight-chain or branched perfluoroalkyl group having 1 to 6 carbon atoms. m is an integer of 1 to 3.

[0094] [Production method of PC copolymer] A method for producing a PC copolymer will be described below by taking the PC copolymer represented by the above general formula (100) as an example. * indicates a bonding position. TIFF0007644093000018.tif25149

[0095] The PC copolymer of this embodiment can be suitably obtained, for example, by the following synthesis reaction (CS1), (CS2) or (CS3). (CS1) A bischloroformate oligomer represented by the following general formula (1A) and a dihydric phenolic compound represented by the following general formula (6) are subjected to interfacial polycondensation in the presence of an acid binder. (CS2) A low-mer bischloroformate oligomer represented by the following general formula (2A) and a dihydric phenolic compound represented by the following general formula (5) are subjected to interfacial polycondensation in the presence of an acid binder. (CS3) A bischloroformate oligomer having a low molecular weight represented by the following general formula (1A) is mixed with a bischloroformate oligomer having a low molecular weight represented by the following general formula (2A), and the mixture of the bischloroformate oligomer represented by the following general formula (1A) and the bischloroformate oligomer represented by the following general formula (2A) is subjected to interfacial polycondensation with a dihydric phenolic compound represented by the following general formula (5) or a dihydric phenolic compound represented by the following general formula (6).

[0096] The above synthesis reactions of the PC copolymers (CS1) to (CS3) are carried out in the presence of at least one of an end-capping agent and a branching agent, if necessary.

[0097] [ka]

[0098] In the general formulas (1A) and (5), Ar 1 is a group represented by the general formula (3). In the general formulas (2A) and (6), Ar 2 is a group represented by general formula (4).

[0099] In the general formula (1A), n1 represents the average number of monomers of the bischloroformate oligomer. The average number of monomers, n1, is 1.0 or more and 1.3 or less, preferably 1.0 or more and 1.2 or less, and more preferably 1.0 or more and 1.1 or less. In the general formula (2A), n2 represents the average number of monomers of the bischloroformate oligomer. The average number of monomers, n2, is 1.0 or more and 1.3 or less, preferably 1.0 or more and 1.2 or less, and more preferably 1.0 or more and 1.1 or less. The PC copolymer of this embodiment can be easily produced by using, as a raw material, at least one of the bischloroformate oligomer represented by the general formula (1A) in which the average number of monomers n1 is in the range of 1.0 or more and 1.3 or less, and the bischloroformate oligomer represented by the general formula (2A) in which the average number of monomers n2 is in the range of 1.0 or more and 1.3 or less. The average number of monomers n1 and n2 can be calculated by the methods described in the Examples below.

[0100] For example, even if a bischloroformate oligomer represented by the general formula (2A) having an average number of monomers n2 of 1.0 is reacted with a comonomer, for example, a terphenyl compound represented by the general formula (5) in a molar ratio of 1:1, the amount of Ar 1 Abundance ratio (Ar 1 / (Ar 1 +Ar 2 )) may be difficult to reach 50 mol %. It is Ar 2 After forming the oligomer (the bischloroformate oligomer represented by the general formula (2A)), Ar 1 When reacting with a monomer containing the above general formula (5) (a terphenyl compound represented by the above general formula (5)), Ar 2 The chloroformate group at the end of the oligomer reacts with the base present in the reaction system to form a hydroxyl group, which is then converted to the Ar 2 This is because polycondensation with oligomers may occur.

[0101] In addition, by using at least one of the bischloroformate oligomer represented by the general formula (1A) having an average number of monomers n1 in the range of 1.0 to 1.3 and the bischloroformate oligomer represented by the general formula (2A) having an average number of monomers n2 in the range of 1.0 to 1.3 as a raw material, it is possible to obtain highly crystalline Ar as described above. 1 Even if the structure is a PC copolymer, the triad fraction of AAA triads (structural units AAA consisting of three consecutive repeating units A) in the PC copolymer can be suppressed to 5 mol % or less. As a result, crystallization of the PC copolymer can be suppressed, resulting in a PC copolymer with good solubility in organic solvents.

[0102] The bischloroformate oligomer represented by the general formula (1A) used in the method for producing the PC copolymer of this embodiment is derived from the terphenyl compound represented by the general formula (5). The bischloroformate oligomer represented by the general formula (2A) used in the method for producing the PC copolymer of this embodiment is derived from a dihydric phenol compound represented by the general formula (6).

[0103] (Monomer represented by formula (5)) The structural unit of the PC copolymer of this embodiment is Ar 1 The monomer (terphenyl compound) represented by the above general formula (5) which is used as the raw material for the above will now be described. Examples of the monomer (terphenyl compound) represented by the general formula (5) include 4,4″-dihydroxy-m-terphenyl, 3,3″-dimethyl-4,4″-dihydroxy-m-terphenyl, 3,3″,5,5″-tetramethyl-4,4″-dihydroxy-m-terphenyl, and 3,3″-diethyl-4,4″-dihydroxy-m-terphenyl.

[0104] From the viewpoint of abrasion resistance, these terphenyl compounds are preferably dihydric phenol monomers whose homopolymers have a solubility in methylene chloride of 2% by mass or less and which crystallize during the polycarbonate synthesis reaction by the interfacial polycondensation method, making it substantially impossible to synthesize homopolymers having a number average molecular weight of 10,000 or more. Whether the solubility in methylene chloride is 2% by mass or less can be confirmed by immersing 2 parts by mass of a solid homopolymer having an organic solvent content of 500 ppm by mass or less and a viscosity average molecular weight in the range of 15,000 to 30,000 inclusive in 98 parts by mass of methylene chloride at room temperature (25°C), leaving it for 24 hours, performing solid-liquid separation, and drying the solid side to determine whether the mass loss is 0.04 parts by mass or more.

[0105] (Monomer represented by formula (6)) The structural unit of the PC copolymer of this embodiment is Ar 2 The dihydric phenol compound (comonomer) represented by the above general formula (6) which is used as the raw material for the above will now be described. The dihydric phenol compound represented by the general formula (6) includes a bisphenol compound. Specifically, for example, 1,1-bis(3-methyl-4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)ethane, 1,2-bis(4-hydroxyphenyl)ethane, 2,2-bis(3-methyl-4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)butane, 1,1-bis(4-hydroxyphenyl)cyclopentane, 1,1-bis(3-methyl-4-hydroxyphenyl)cyclopentane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(3-methyl-4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, bis(3-methyl-4-hydroxyphenyl)methane, 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)-1,1-diphenylmethane, 1,1-bis(4-hydroxyphenyl)-1-furan, phenylethane, 1,1-bis(4-hydroxyphenyl)-1-phenylmethane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, 1,1-bis(3-ethyl-4-hydroxyphenyl)cyclohexane, 2,2-bis(3-trifluoromethyl-4-hydroxyphenyl)ethane, 2,2-bis(3-pentafluoroethyl-4-hydroxyphenyl)ethane, 2,2-bis(2-methyl-4-hydroxyphenyl)propane, 2,2-bis(3-trifluoromethyl-4-hydroxyphenyl)propane, 2,2-bis(3-pentafluoroethyl-4-hydroxyphenyl)propane, 1,1-bis(3-trifluoromethyl-4-hydroxyphenyl)cyclohexane, and 1,1-bis(3-pentafluoroethyl-4-hydroxyphenyl)cyclohexane.

[0106] Among these bisphenol compounds, 2,2-bis(4-hydroxyphenyl)butane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)cyclohexane, and 1,1-bis(3-methyl-4-hydroxyphenyl)cyclohexane are preferred in that they provide PC copolymers with excellent abrasion resistance and solubility in organic solvents. In addition, they are preferred because they provide good coating solutions when used as PC copolymers for electrophotographic photoreceptors. These bisphenol compounds may be used alone or in combination of two or more.

[0107] (End-capping agent) In the method for producing a PC copolymer according to this embodiment, the end-capping agent that generates the chain ends can be, for example, a monovalent carboxylic acid or a derivative thereof, or a monovalent phenol. For example, p-tert-butyl-phenol, p-phenylphenol, p-cumylphenol, p-perfluorononylphenol, p-(perfluorononylphenyl)phenol, p-(perfluorohexyl)phenol, p-tert-perfluorobutylphenol, perfluorooctylphenol, perfluorohexylphenol, 1-(p-hydroxybenzyl)perfluorodecane, p-[2-(1H,1H-perfluorotridodecyloxy)-1,1,1,3,3,3-hexafluoropropyl]phenol, 3,5-bis(perfluorohexyloxycarbonyl)phenol, p-hydroxybenzoic acid perfluorododecyl, p-(1H,1H-perfluorooctyloxy)phenol, 2H,2H,9H-perfluorononanoic acid, and 1,1,1,3,3,3-tetrafluoro-2-propanol can be mentioned.

[0108] As an end-capping agent for generating a chain end, a fluorine-containing alcohol represented by the above general formula (30) or (31), or a monohydric fluorine-containing alcohol such as 1,1,1,3,3,3-hexafluoro-2-propanol is also preferably used. It is also preferable to use a fluorine-containing alcohol via an ether bond represented by the above general formula (32), (33), or (34).

[0109] Among these, it is preferable to use, as the end-capping agent for generating the chain end, the monohydric phenol represented by the general formula (9) or the monohydric fluorine-containing alcohol represented by the general formula (10) from the viewpoint of improving electrical properties and abrasion resistance.

[0110] As the monohydric phenol represented by the general formula (9), for example, p-tert-butyl-phenol, p-perfluorononylphenol, p-perfluorohexylphenol, p-tert-perfluorobutylphenol, p-perfluorooctylphenol, etc. are preferably used. That is, in this embodiment, it is preferable that the chain ends are blocked with an end blocking agent selected from the group consisting of p-tert-butyl-phenol, p-perfluorononylphenol, p-perfluorohexylphenol, p-tert-perfluorobutylphenol, and p-perfluorooctylphenol.

[0111] Examples of the fluorine-containing alcohol via an ether bond represented by the general formula (10) include the following compounds. That is, the chain end of the present embodiment may be preferably blocked with an end blocking agent selected from any one of the following fluorine-containing alcohols.

[0112] [ka]

[0113] As the monovalent phenol that is the end-capping agent, a compound in which a monovalent organic siloxane-modified phenyl group is converted into a monovalent phenol can also be suitably used. An example of the monovalent organosiloxane-modified phenyl group is a group represented by the following formula (9).

[0114] [ka]

[0115] In the above general formula (9), Z is a hydrocarbon group having 2 to 6 carbon atoms. It is preferably an alkylene group, and more preferably a methylene group having 2 to 4 repeating units. R 41 is an aliphatic hydrocarbon group having 1 to 6 carbon atoms, preferably an alkyl group having 1 to 6 carbon atoms. R 42 ~R 45 each independently represents a hydrogen atom, a substituted or unsubstituted alkyl group having 1 to 12 carbon atoms, a substituted or unsubstituted alkoxy group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 ring carbon atoms. R 46 ~R 49 each independently represents a substituted or unsubstituted alkyl group having 1 to 12 carbon atoms or a substituted or unsubstituted aryl group having 6 to 12 ring carbon atoms. Examples of the substituted or unsubstituted alkyl group having 1 to 12 carbon atoms and the substituted or unsubstituted aryl group having 6 to 12 ring carbon atoms include R 3 and R 4 The alkyl group is preferably a methyl group, and the aryl group is preferably a phenyl group. n is an integer of 2 to 600, and indicates the average number of repeating units when the polymer has a molecular weight distribution.

[0116] Examples of the monovalent organosiloxane-modified phenyl group include the following groups:

[0117] [ka]

[0118] In an electrophotographic photoreceptor using a PC copolymer having a monovalent organosiloxane-modified phenyl group as a binder resin, adhesion of foreign matter such as toner can be reduced. When the PC copolymer of the present embodiment has a monovalent organosiloxane-modified phenyl group, the proportion of the monovalent organosiloxane-modified phenyl group is preferably 0.01% by mass or more, more preferably 50% by mass or less, more preferably 0.1% by mass or more and 20% by mass or less, and particularly preferably 0.5% by mass or more and 10% by mass or less, based on the total mass of the PC copolymer.

[0119] The proportion of the terminal blocking agent added is preferably 0.05 mol% to 30 mol%, more preferably 0.1 mol% to 10 mol%, expressed as the molar percentage (copolymerization composition ratio) of the copolymerization composition of the repeating unit A, the repeating unit B, and the chain end. When the proportion of the terminal blocking agent added is 30 mol% or less, the decrease in mechanical strength can be suppressed. When the proportion of the terminal blocking agent added is 0.05 mol% or more, the decrease in moldability can be suppressed.

[0120] The branching agent that can be used in the method for producing the PC copolymer of the present embodiment is not particularly limited. Specific examples of the branching agent include phloroglucin, pyrogallol, 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)-2-heptene, 2,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)-3-heptene, 2,4-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(2-hydroxyphenyl)benzene, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, tris(4-hydroxyphenyl)phenylmethane, 2,2-bis[4,4-bis(4-hydroxyphenyl)cyclohexyl]propane, 2,4-bis[2-bis(4- 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, 2-(4-hydroxyphenyl)-2-(2,4-dihydroxyphenyl)propane, tetrakis(4-hydroxyphenyl)methane, tetrakis[4-(4-hydroxyphenylisopropyl)phenoxy]methane, 2,4-dihydroxybenzoic acid, trimesic acid, cyanuric acid, 3,3-bis(3-methyl-4-hydroxyphenyl)-2-oxo-2,3-dihydroindole, 3,3-bis(4-hydroxyaryl)oxindole, 5-chloroisatin, 5,7-dichloroisatin, and 5-bromoisatin.

[0121] The proportion of the branching agent added is preferably 30 mol % or less, more preferably 5 mol % or less, in terms of copolymer composition ratio. When the proportion of the branching agent added is 30 mol % or less, deterioration of moldability can be suppressed.

[0122] In the case of carrying out interfacial polycondensation, examples of the acid binder include alkali metal hydroxides (e.g., sodium hydroxide, potassium hydroxide, lithium hydroxide, cesium hydroxide, etc.), alkaline earth metal hydroxides (e.g., magnesium hydroxide, calcium hydroxide, etc.), weak alkali metal acid salts (e.g., sodium carbonate, potassium carbonate, calcium acetate, etc.), weak alkaline earth metal acid salts, and organic bases (e.g., pyridine, etc.). When performing interfacial polycondensation, preferred acid binders are alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and calcium hydroxide, and alkaline earth metal hydroxides. These acid binders can also be used as a mixture. The proportion of the acid binder used can be appropriately adjusted in consideration of the stoichiometric ratio (equivalents) of the reaction. Specifically, 1 equivalent or an excess of the acid binder can be used per mole of the total hydroxyl groups of the dihydric phenol raw material, and preferably 1 equivalent or more and 10 equivalents or less of the acid binder can be used.

[0123] The solvent used in the method for producing the PC copolymer of the present embodiment may be any solvent that exhibits a certain level of solubility for the resulting copolymer. Suitable examples of the solvent include aromatic hydrocarbons (e.g., toluene, xylene, etc.), halogenated hydrocarbons (e.g., methylene chloride, chloroform, 1,1-dichloroethane, 1,2-dichloroethane, 1,1,1-trichloroethane, 1,1,2-trichloroethane, 1,1,1,2-tetrachloroethane, 1,1,2,2-tetrachloroethane, pentachloroethane, and chlorobenzene, etc.), ketones (e.g., cyclohexanone, acetone, and acetophenone, etc.), and ethers (tetrahydrofuran and 1,4-dioxane, etc.). These solvents may be used alone or in combination of two or more. Furthermore, the interfacial polycondensation reaction may be carried out using two solvents that are not miscible with each other.

[0124] The catalyst used in the method for producing the PC copolymer of the present embodiment is not particularly limited. For example, tertiary amines (e.g., trimethylamine, triethylamine, tributylamine, N,N-dimethylcyclohexylamine, pyridine, N,N-diethylaniline, and N,N-dimethylaniline, etc.), quaternary ammonium salts (e.g., trimethylbenzylammonium chloride, triethylbenzylammonium chloride, tributylbenzylammonium chloride, trioctylmethylammonium chloride, tetrabutylammonium chloride, and tetrabutylammonium bromide, etc.), and quaternary phosphonium salts (e.g., tetrabutylphosphonium chloride and tetrabutylphosphonium bromide, etc.) are suitable. Furthermore, if necessary, a small amount of an antioxidant such as sodium sulfite or a hydrosulfite salt may be added to the reaction system of the PC copolymer of this embodiment.

[0125] The method for producing a PC copolymer according to this embodiment can be carried out in various other specific modes in addition to the above-mentioned method for producing a PC copolymer. For example, a terphenyl compound represented by the general formula (5) is reacted with phosgene or the like to produce a bischloroformate oligomer having a low number of monomers represented by the general formula (1A). Then, this bischloroformate oligomer is reacted with a dihydric phenolic compound represented by the general formula (6) in the presence of a mixed solution of the solvent and an aqueous alkaline solution of an acid binder. This method can be used to remove Ar in the PC copolymer. 1 / (Ar 1 +Ar 2 ) can be adjusted to a preferred range.

[0126] A method for producing a bischloroformate oligomer having an n1 value in the range of 1.0 or more and 1.3 or a bischloroformate oligomer having an n2 value in the range of 1.0 or more and 1.3 or less in the general formula (1A) is shown in detail in the production examples described later, but is roughly as follows. First, the terphenyl compound represented by the general formula (5) or the dihydric phenolic compound represented by the general formula (6) is suspended in a hydrophobic solvent such as methylene chloride, and phosgene is further added to form a first solution. Meanwhile, a tertiary amine such as triethylamine is dissolved in a hydrophobic solvent such as methylene chloride to form a second solution, which is then added dropwise to the first solution to react at a temperature below room temperature (25°C). The third solution containing the obtained reaction mixture is washed with hydrochloric acid and pure water to obtain an organic layer containing a polycarbonate oligomer with a low monomer number. The dropping temperature and the reaction temperature are usually from 0° C. to 70° C., preferably from 5° C. to 65° C. The dropping time and the reaction time are both usually from 15 minutes to 4 hours, preferably from 30 minutes to 3 hours. The average number of monomers n1 and the average number of monomers n2 of the bischloroformate oligomer thus obtained, represented by the general formula (1A) or (2A), are each independently 1.0 or more and 1.3 or less, preferably 1.0 or more and 1.2 or less, and more preferably 1.0 or more and 1.1 or less. Use of the bischloroformate oligomer produced by this production method is preferable in that it can simplify the washing step during the production of a PC copolymer.

[0127] The dihydric phenolic compound (monomer) represented by the general formula (6) is added to the organic layer containing the thus obtained bischloroformate oligomer having a low molecular weight represented by the general formula (1A) and reacted with the dihydric phenolic compound (monomer) represented by the general formula (6). Alternatively, the dihydric phenolic compound (monomer) represented by the general formula (5) is added to the organic layer containing the bischloroformate oligomer having a low molecular weight represented by the general formula (2A) and reacted with the dihydric phenolic compound (monomer).

[0128] The reaction temperature is preferably 0°C or higher and 150°C or lower, more preferably 5°C or higher and 40°C or lower, and further preferably 10°C or higher and 25°C or lower. The reaction pressure may be reduced, normal, or increased, but is usually preferably normal pressure or the pressure of the reaction system. The reaction time depends on the reaction temperature, but is usually 0.5 minutes to 10 hours, preferably 1 minute to 3 hours.

[0129] In this reaction, the terphenyl compound represented by the general formula (5) or the dihydric phenolic compound represented by the general formula (6) is preferably added as an aqueous solution or an organic solvent solution. There is no particular restriction on the order of addition. In addition, in the above-mentioned production method, the catalyst, the end-capping agent, the branching agent, etc. can be added, if necessary, either during the production of the bischloroformate oligomer or during the subsequent reaction for polymerizing, or both.

[0130] The PC copolymer obtained as described above is a copolymer comprising the repeating unit A represented by the above general formula (1) and the repeating unit B represented by the above general formula (2). Furthermore, this PC copolymer may contain polycarbonate units having structural units other than the repeating unit A and the repeating unit B, or units having a polyester or polyether structure, as long as the achievement of the object of the present invention is not impaired.

[0131] The reduced viscosity of the resulting PC copolymer [η SP / C] can be adjusted to the above range by various methods, for example, by selecting the reaction conditions, adjusting the amounts of the branching agent and the end-capping agent, etc. In addition, the obtained PC copolymer may be subjected to at least one of physical treatments (e.g., mixing and fractionation) and chemical treatments (e.g., polymer reaction, crosslinking treatment, partial decomposition treatment, etc.) to obtain a desired reduced viscosity [η SP It can also be obtained as a PC copolymer of [C]. The resulting reaction product (crude product) can be subjected to various post-treatments such as known separation and purification methods to recover a PC copolymer with a desired purity (degree of purification).

[0132] [Coating Fluid Composition] The coating liquid of the present embodiment contains at least the PC copolymer of the present embodiment and an organic solvent capable of dissolving or dispersing the PC copolymer. The coating liquid may contain additives such as low molecular weight compounds, colorants (e.g., dyes and pigments), functional compounds (e.g., charge transport materials, electron transport materials, hole transport materials, and charge generating materials), fillers (e.g., inorganic or organic fillers, fibers, and fine particles), antioxidants, ultraviolet absorbers, and acid scavengers, in addition to the PC copolymer and organic solvent. Examples of substances that may be contained in addition to the PC copolymer include substances contained in the components of the electrophotographic photoreceptor described below. The coating liquid may contain other resins as long as they do not impair the effects of the present invention, and examples of such resins are listed below as examples of the components of the electrophotographic photoreceptor. The organic solvent used in the present embodiment may be used alone or in combination with a plurality of solvents, taking into consideration the solubility, dispersibility, viscosity, evaporation rate, chemical stability, and stability against physical changes of the PC copolymer of the present embodiment and other materials. Examples of such resins are listed below as examples of the components of the electrophotographic photoreceptor.

[0133] The concentration of the PC copolymer component in the coating liquid of this embodiment may be an appropriate viscosity according to the use of the coating liquid. The concentration of the PC copolymer component in the coating liquid is preferably 0.1% by mass or more and 40% by mass or less, more preferably 1% by mass or more and 35% by mass or less, and even more preferably 5% by mass or more and 30% by mass or less. If the concentration of the PC copolymer component in the coating liquid is 40% by mass or less, the viscosity does not become too high and the coatability is good. If it is 0.1% by mass or more, the viscosity can be kept at an appropriate level, and a homogeneous film can be obtained. In addition, the concentration is appropriate for shortening the drying time after coating and easily achieving the target film thickness.

[0134] The PC copolymer of this embodiment has good compatibility with the charge transport material, and is unlikely to whiten or gel when dissolved in the organic solvent. Therefore, the coating liquid of this embodiment containing the PC copolymer and an organic solvent can suppress whitening or gelling of the PC polymer component over a long period of time, even when it further contains a charge transport material, and can be stored stably. In addition, when the photosensitive layer of an electrophotographic photoreceptor is formed using this coating liquid (coating liquid containing a charge transport material), the photosensitive layer can be suppressed from crystallizing, and an excellent electrophotographic photoreceptor can be produced that does not cause defects in image quality. When the coating liquid of the present embodiment contains a PC copolymer and a charge transport material, the ratio of the PC copolymer to the charge transport material in the coating liquid is usually 20:80 to 80:20 by mass, and preferably 30:70 to 70:30. In the coating liquid of this embodiment, the PC copolymer of this embodiment may be used alone or in combination of two or more kinds.

[0135] The coating liquid of the present embodiment is usually suitably used for forming the charge transport layer of a multi-layer electrophotographic photoreceptor, the photosensitive layer of which includes at least a charge generation layer and a charge transport layer. In addition, by further adding the charge generation material to the coating liquid, the coating liquid can also be used for forming the photosensitive layer of a single-layer electrophotographic photoreceptor. In addition, the coating liquid of the present embodiment has excellent moldability, and is therefore suitable for use in forming a molded body. Furthermore, when a molded article is formed using the coating liquid of the present embodiment, crystallization of the molded article can be suppressed, resulting in a molded article with high transparency.

[0136] [Composition of molded body] At least one of the PC copolymer of this embodiment and the coating liquid of this embodiment can be used to form a molded article. The molded article may be, for example, an optical member, and the optical member may be, for example, an electrophotographic photoreceptor and an optical lens. In addition, when the substrate is a film, the laminated film as one embodiment of the molded article may be applied as, for example, an in-mold molding film and a decorative film. In addition, the laminated film may be applied as a touch panel film used in liquid crystal and organic EL displays, an optical film such as an optical compensation film and an anti-reflection film, and a conductive film. A molded article containing the PC copolymer of this embodiment is resistant to whitening and has excellent transparency, as well as excellent mechanical strength such as abrasion resistance and electrical strength.

[0137] [Configuration of electrophotographic photoreceptor] The electrophotographic photoreceptor of the present embodiment contains the PC copolymer of the present embodiment. An electrophotographic photoreceptor according to one embodiment has a substrate and a photosensitive layer provided on the substrate, and the photosensitive layer contains the PC copolymer of this embodiment. The electrophotographic photoreceptor of this embodiment may be any electrophotographic photoreceptor, including various known types of electrophotographic photoreceptors, so long as the PC copolymer of this embodiment is used in the photosensitive layer. However, it is preferred that the photosensitive layer is a multi-layer type electrophotographic photoreceptor having at least one charge generation layer and at least one charge transport layer, or a single-layer type electrophotographic photoreceptor having a charge generation material and a charge transport material in one layer.

[0138] The PC copolymer may be used in any part of the photosensitive layer, but in order to fully exert the effects of this embodiment, it is preferable to use it as a binder resin for a charge transport material in a charge transport layer or as a binder resin for a single photosensitive layer. It is also preferable to use it not only in the photosensitive layer but also in a surface protective layer. In the case of a multi-layered electrophotographic photoreceptor having two charge transport layers, it is preferable to use it in one of the charge transport layers. In the electrophotographic photoreceptor of the present embodiment, the PC copolymer of the present embodiment may be used alone or in combination of two or more. If desired, other binder resin components such as polycarbonates may be contained within a range that does not impair the object of the present embodiment. Furthermore, additives such as antioxidants may be contained.

[0139] The electrophotographic photoreceptor of this embodiment has a photosensitive layer on a conductive substrate. When the photosensitive layer has a charge generation layer and a charge transport layer, the charge transport layer may be laminated on the charge generation layer, or conversely, the charge generation layer may be laminated on the charge transport layer. The photosensitive layer may also contain a charge generation material and a charge transport material simultaneously in one layer. Furthermore, a conductive or insulating protective film may be formed on the surface layer as necessary. By using the PC copolymer of this embodiment in the surface layer, an electrophotographic photoreceptor with excellent wear resistance can be obtained. Furthermore, intermediate layers such as an adhesive layer for improving adhesion between layers or a blocking layer for blocking charges may be formed.

[0140] As the conductive substrate material used in the electrophotographic photoreceptor of this embodiment, various materials such as known materials can be used. Specifically, plates, drums, and sheets made of aluminum, nickel, chromium, palladium, titanium, molybdenum, indium, gold, platinum, silver, copper, zinc, brass, stainless steel, lead oxide, tin oxide, indium oxide, ITO (indium tin oxide: tin-doped indium oxide) or graphite; films, sheets, or seamless belts made of glass, cloth, paper, and plastic that have been treated to be conductive by coating by vapor deposition, sputtering, painting, or the like; and metal drums that have been treated to be metal oxidized by electrode oxidation or the like can be used.

[0141] The charge generation layer has at least a charge generation material. This charge generation layer can be obtained by forming a layer of the charge generation material on the substrate as the base by vacuum deposition or sputtering, or by forming a layer of the charge generation material bound to the substrate as the base by using a binder resin. Various methods, including known methods, can be used to form a charge generation layer using a binder resin. Usually, for example, a method is suitable in which a coating liquid in which the charge generation material is dispersed or dissolved together with the binder resin in a suitable solvent is applied onto a substrate as a given base, and then dried to obtain a wet molded body.

[0142] As the charge generating material in the charge generating layer, various known materials can be used. Specific compounds include selenium alone (e.g., amorphous selenium, trigonal selenium, etc.), selenium alloys (e.g., selenium-tellurium, etc.), selenium compounds or selenium-containing compositions (e.g., As2Se3, etc.), inorganic materials consisting of elements in Groups 12 and 16 of the periodic table (e.g., zinc oxide, CdS-Se, etc.), oxide-based semiconductors (e.g., titanium oxide, etc.), silicon-based materials (e.g., amorphous silicon, etc.), metal-free phthalocyanine pigments (e.g., , τ-type metal-free phthalocyanine, and χ-type metal-free phthalocyanine, etc.), metal phthalocyanine pigments (for example, α-type copper phthalocyanine, β-type copper phthalocyanine, γ-type copper phthalocyanine, ε-type copper phthalocyanine, X-type copper phthalocyanine, A-type titanyl phthalocyanine, B-type titanyl phthalocyanine, C-type titanyl phthalocyanine, D-type titanyl phthalocyanine, E-type titanyl phthalocyanine, F-type titanyl phthalocyanine, G-type titanyl phthalocyanine, Examples of the pigments include H-type titanyl phthalocyanine, K-type titanyl phthalocyanine, L-type titanyl phthalocyanine, M-type titanyl phthalocyanine, N-type titanyl phthalocyanine, Y-type titanyl phthalocyanine, oxo-titanyl phthalocyanine, titanyl phthalocyanine that exhibits a strong diffraction peak at a Bragg angle 2θ of 27.3±0.2 degrees in an X-ray diffraction diagram, and gallium phthalocyanine), cyanine dyes, anthracene pigments, bisazo pigments, pyrene pigments, polycyclic quinone pigments, quinacridone pigments, indigo pigments, perylene pigments, pyrylium dyes, squalium pigments, anthanthrone pigments, benzimidazole pigments, azo pigments, thioindigo pigments, quinoline pigments, lake pigments, oxazine pigments, dioxazine pigments, triphenylmethane pigments, azulenium dyes, triarylmethane dyes, xanthine dyes, thiazine dyes, thiapyrylium dyes, polyvinyl carbazole, and bisbenzimidazole pigments. These compounds can be used alone or in combination as a charge generating substance. Among these charge generating substances, preferred charge generating substances include those specifically described in JP-A-11-172003.

[0143] The charge transport layer can be obtained as a wet molded body by forming a layer in which a charge transport material is bound with a binder resin on a substrate serving as a base. The binder resin of the charge generating layer or the charge transport layer is not particularly limited, and various known resins can be used.Specifically, for example, polystyrene, polyvinyl chloride, polyvinyl acetate, vinyl chloride-vinyl acetate copolymer, polyvinyl acetal, alkyd resin, acrylic resin, polyacrylonitrile, polycarbonate, polyurethane, epoxy resin, phenol resin, polyamide, polyketone, polyacrylamide, butyral resin, polyester resin, vinylidene chloride-vinyl chloride copolymer, methacrylic resin, styrene-butadiene copolymer, vinylidene chloride-acrylonitrile copolymer, vinyl chloride-vinyl acetate-maleic anhydride copolymer, silicone resin, silicone alkyd resin, phenol-formaldehyde resin, styrene-alkyd resin, melamine resin, polyether resin. , benzoguanamine resin, epoxy acrylate resin, urethane acrylate resin, poly-N-vinyl carbazole, polyvinyl butyral, polyvinyl formal, polysulfone, casein, gelatin, polyvinyl alcohol, ethyl cellulose, nitrocellulose, carboxy-methyl cellulose, vinylidene chloride polymer latex, acrylonitrile-butadiene copolymer, vinyl toluene-styrene copolymer, soybean oil modified alkyd resin, nitrated polystyrene, polymethylstyrene, polyisoprene, polythiocarbonate, polyarylate, polyhaloarylate, polyallyl ether, polyvinyl acrylate, and polyester acrylate. These may be used alone or in combination of two or more. As the binder resin in the charge generating layer and / or charge transport layer, it is preferable to use the PC copolymer of the present embodiment described above.

[0144] The charge transport layer can be formed by any of various known methods, but a suitable method is to apply a coating liquid in which a charge transport material is dispersed or dissolved in a suitable solvent together with the PC copolymer of this embodiment onto a substrate as a given base, and then dry the resulting liquid to obtain a wet molded body. The blending ratio of the charge transport material and the PC copolymer used to form the charge transport layer is preferably 20:80 to 80:20 by mass, more preferably 30:70 to 70:30. In the charge transport layer, the PC copolymer of the present embodiment may be used alone or in combination with two or more kinds. In addition, other binder resins may be used in combination with the PC copolymer of the present embodiment within a range that does not impair the object of the present embodiment.

[0145] The thickness of the charge transport layer thus formed is usually about 5 μm to 100 μm, preferably 10 μm to 50 μm, and more preferably 15 μm to 35 μm. If the thickness is 5 μm or more, the initial charge potential does not decrease, and if it is 100 μm or less, the deterioration of electrophotographic properties can be prevented. As the charge transport material that can be used together with the PC copolymer of the present embodiment, various known compounds can be used.As such compounds, for example, carbazole compounds, indole compounds, imidazole compounds, oxazole compounds, pyrazole compounds, oxadiazole compounds, pyrazoline compounds, thiadiazole compounds, aniline compounds, hydrazone compounds, aromatic amine compounds, aliphatic amine compounds, stilbene compounds, fluorenone compounds, butadiene compounds, quinone compounds, quinodimethane compounds, thiazole compounds, triazole compounds, imidazolone compounds, imidazolidine compounds, bisimidazolidine compounds, oxazolone compounds, benzothiazole compounds, benzimidazole compounds, quinazoline compounds, benzofuran compounds, acridine compounds, phenazine compounds, poly-N-vinylcarbazole, polyvinylpyrene, polyvinylanthracene, polyvinylacridine, poly-9-vinylphenylanthracene, pyrene-formaldehyde resin, ethylcarbazole resin, or polymers having these structures in the main chain or side chain, etc. are preferably used. These compounds may be used alone or in combination of two or more. Among these charge transporting substances, the compounds specifically exemplified in JP-A-11-172003 and the charge transporting substances represented by the following structures are particularly preferably used.

[0146] [ka]

[0147] [ka]

[0148] [ka]

[0149] [ka]

[0150]

change

[0151]

change

[0152]

change

[0153]

change

[0154]

change

[0155]

change

[0156]

change

[0157]

change

[0158]

change

[0159]

change

[0160] In the electrophotographic photoreceptor of the present embodiment, it is preferable to use the PC copolymer of the present embodiment as a binder resin in at least one of the charge generating layer and the charge transport layer.

[0161] In the electrophotographic photoreceptor of this embodiment, a commonly used undercoat layer can be provided between the conductive substrate and the photosensitive layer. For this undercoat layer, for example, fine particles (e.g., titanium oxide, aluminum oxide, zirconia, titanic acid, zirconic acid, lanthanum lead, titanium black, silica, lead titanate, barium titanate, tin oxide, indium oxide, silicon oxide, etc.), polyamide resin, phenolic resin, casein, melamine resin, benzoguanamine resin, polyurethane resin, epoxy resin, cellulose, nitrocellulose, polyvinyl alcohol, and polyvinyl butyral resin can be used. In addition, as the resin used in this undercoat layer, the binder resin may be used, or the PC copolymer of this embodiment may be used. These fine particles and resins can be used alone or in various mixtures. When using them as a mixture, it is preferable to use inorganic fine particles and resin in combination because a coating with good smoothness is formed.

[0162] The thickness of the undercoat layer is from 0.01 μm to 10 μm, preferably from 0.1 μm to 7 μm. If the thickness is 0.01 μm or more, the undercoat layer can be formed uniformly, and if the thickness is 10 μm or less, deterioration of electrophotographic properties can be suppressed. In addition, a known blocking layer that is commonly used can be provided between the conductive substrate and the photosensitive layer. The same resin as the binder resin can be used as the blocking layer. The PC copolymer of this embodiment can also be used. The thickness of this blocking layer is 0.01 μm or more and 20 μm or less, preferably 0.1 μm or more and 10 μm or less. If the thickness is 0.01 μm or more, the blocking layer can be formed uniformly, and if the thickness is 20 μm or less, the deterioration of electrophotographic properties can be suppressed.

[0163] Furthermore, in the electrophotographic photoreceptor of this embodiment, a protective layer may be laminated on the photosensitive layer. The same type of resin as the binder resin may be used for this protective layer. It is particularly preferable to use the PC copolymer of this embodiment. The thickness of this protective layer is 0.01 μm or more and 20 μm or less, preferably 0.1 μm or more and 10 μm or less. This protective layer may contain the charge generating material, the charge transport material, additives, metals and their oxides, nitrides, or salts, alloys, carbon black, and conductive materials such as organic conductive compounds.

[0164] Furthermore, in order to improve the performance of this electrophotographic photoreceptor, the charge generating layer and the charge transport layer may contain binders, plasticizers, curing catalysts, fluidity imparting agents, pinhole control agents, and spectral sensitivity sensitizers (sensitizing dyes), etc. Also, in order to prevent an increase in residual potential, a decrease in charging potential, and a decrease in sensitivity due to repeated use, various additives such as chemical substances, antioxidants, surfactants, curl inhibitors, and leveling agents may be added.

[0165] Examples of the binder include silicone resin, polyamide resin, polyurethane resin, polyester resin, epoxy resin, polyketone resin, polycarbonate copolymer, polystyrene resin, polymethacrylate resin, polyacrylamide resin, polybutadiene resin, polyisoprene resin, melamine resin, benzoguanamine resin, polychloroprene resin, polyacrylonitrile resin, ethyl cellulose resin, nitrocellulose resin, urea resin, phenol resin, phenoxy resin, polyvinyl butyral resin, formal resin, vinyl acetate resin, vinyl acetate / vinyl chloride copolymer resin, and polyester carbonate resin. At least one of a thermosetting resin and a photocurable resin can also be used. In any case, there is no particular restriction as long as the resin is electrically insulating and can form a film under normal conditions and does not impair the effects of the present invention.

[0166] Specific examples of the plasticizer include biphenyl, chlorinated biphenyl, o-terphenyl, halogenated paraffin, dimethylnaphthalene, dimethyl phthalate, dibutyl phthalate, dioctyl phthalate, diethylene glycol phthalate, triphenyl phosphate, diisobutyl adipate, dimethyl sebacate, dibutyl sebacate, butyl laurate, methylphthalyl ethyl glycolate, dimethyl glycol phthalate, methylnaphthalene, benzophenone, polypropylene, polystyrene, and fluorohydrocarbons.

[0167] Specific examples of the curing catalyst include methanesulfonic acid, dodecylbenzenesulfonic acid, and dinonylnaphthalenedisulfonic acid, examples of the fluidity imparting agent include Modaflow and Acronal 4F, and examples of the pinhole control agent include benzoin and dimethyl phthalate. These plasticizers, curing catalysts, fluidity imparting agents, and pinhole control agents are preferably used in an amount of 5% by mass or less relative to the charge transport material.

[0168] In addition, when a sensitizing dye is used, suitable spectral sensitivity sensitizers include, for example, triphenylmethane dyes (e.g., methyl violet, crystal violet, night blue, and Victoria blue), acridine dyes (e.g., erythrosine, rhodamine B, rhodamine 3R, acridine orange, and frappeosine), thiazine dyes (e.g., methylene blue and methylene green), oxazine dyes (capri blue and meldola blue), cyanine dyes, merocyanine dyes, styryl dyes, pyrylium salt dyes, and thiopyrylium salt dyes.

[0169] An electron-accepting substance can be added to the photosensitive layer for the purpose of improving sensitivity, reducing residual potential, reducing fatigue during repeated use, etc. Specific examples thereof include succinic anhydride, maleic anhydride, dibromomaleic anhydride, phthalic anhydride, tetrachlorophthalic anhydride, tetrabromophthalic anhydride, 3-nitrophthalic anhydride, 4-nitrophthalic anhydride, pyromellitic anhydride, mellitic anhydride, tetracyanoethylene, tetracyanoquinodimethane, o-dinitrobenzene, m-dinitrobenzene, 1,3,5-trinitrobenzene, p-nitrobenzonitrile, picryl chloride, quinone chlorimide, chloranil, bromanil, benzoquinone, 2,3-dichlorobenzoquinone, dichlorodicyanoparabenzoquinone, naphthoquinone, diphenoquinone, tropoquinone, anthraquinone, 1-chloroanthraquinone, dinitroanthraquinone, 4-nitrobenzophenone, 4,4'-dinitro Compounds having a large electron affinity, such as benzophenone, 4-nitrobenzalmalondinitrile, α-cyano-β-(p-cyanophenyl)ethyl acrylate, 9-anthracenylmethylmalondinitrile, 1-cyano-(p-nitrophenyl)-2-(p-chlorophenyl)ethylene, 2,7-dinitrofluorenone, 2,4,7-trinitrofluorenone, 2,4,5,7-tetranitrofluorenone, 9-fluorenylidene-(dicyanomethylenemalononitrile), polynitro-9-fluorenylidene-(dicyanomethylenemalononitrile), picric acid, o-nitrobenzoic acid, p-nitrobenzoic acid, 3,5-dinitrobenzoic acid, pentafluorobenzoic acid, 5-nitrosalicylic acid, 3,5-dinitrosalicylic acid, phthalic acid, and mellitic acid, are preferred. These compounds may be added to either the charge generation layer or the charge transport layer, and the mixing ratio is from 0.01 to 200 parts by weight, preferably from 0.1 to 50 parts by weight, based on 100 parts by weight of the charge generation substance or charge transport substance.

[0170] In addition, in order to improve the surface properties, tetrafluoroethylene resin, trifluorochloroethylene resin, tetrafluoroethylene hexafluoropropylene resin, vinyl fluoride resin, vinylidene fluoride resin, difluorodichloroethylene resin, copolymers thereof, and fluorine-based graft polymers may be used. The blending ratio of these surface modifiers is 0.1% by mass or more and 60% by mass or less, preferably 5% by mass or more and 40% by mass or less, based on the binder resin. If the blending ratio is 0.1% by mass or more, the surface durability and surface energy reduction, etc., of the surface modification are sufficient, and if it is 60% by mass or less, the electrophotographic properties are not deteriorated.

[0171] The antioxidant is preferably, for example, a hindered phenol-based antioxidant, an aromatic amine-based antioxidant, a hindered amine-based antioxidant, a sulfide-based antioxidant, an organic phosphoric acid-based antioxidant, etc. The blending ratio of these antioxidants is usually 0.01% by mass or more and 10% by mass or less, preferably 0.1% by mass or more and 2% by mass or less, based on the charge transport material. As specific examples of such antioxidants, the compounds represented by the chemical formulas [Chemical formula 94] to [Chemical formula 101] described in the specification of JP-A-11-172003 are suitable. These antioxidants may be used alone or in combination of two or more. They may be added to the photosensitive layer, as well as to the surface protective layer, undercoat layer, and blocking layer.

[0172] Specific examples of the solvent used in forming at least one of the charge generating layer and the charge transport layer include aromatic solvents (e.g., benzene, toluene, xylene, and chlorobenzene), ketones (e.g., acetone, methyl ethyl ketone, and cyclohexanone), alcohols (e.g., methanol, ethanol, and isopropanol), esters (e.g., ethyl acetate and ethyl cellosolve), halogenated hydrocarbons (e.g., carbon tetrachloride, carbon tetrabromide, chloroform, dichloromethane, tetrachloroethane), ethers (e.g., tetrahydrofuran, dioxolane, and dioxane), sulfoxides (e.g., dimethyl sulfoxide), and amides (e.g., dimethylformamide, diethylformamide). These solvents may be used alone or in combination of two or more.

[0173] The photosensitive layer of the single-layer electrophotographic photoreceptor can be easily formed by using the charge generating material, charge transport material, and additives, and applying the PC copolymer of the present embodiment as a binder resin. As the charge transport material, it is preferable to add at least one of the hole transport material and the electron transport material described above. As the electron transport material, the electron transport material exemplified in JP-A-2005-139339 can be preferably applied. The application of each layer can be carried out using various types of application equipment such as known equipment. Specifically, for example, an applicator, a spray coater, a bar coater, a tip coater, a roll coater, a dip coater, a doctor blade, or the like can be used.

[0174] The thickness of the photosensitive layer in the electrophotographic photoreceptor is 5 μm to 100 μm, preferably 10 μm to 50 μm, and more preferably 15 μm to 35 μm. If it is 5 μm or more, it is possible to prevent the initial potential from becoming low, and if it is 100 μm or less, it is possible to suppress the deterioration of electrophotographic characteristics. The ratio of the charge generating material to the binder resin used in the manufacture of the electrophotographic photoreceptor is 1:99 to 30:70, preferably 3:97 to 15:85, by mass. The ratio of the charge transport material to the binder resin is 10:90 to 80:20, preferably 30:70 to 70:30, by mass.

[0175] The electrophotographic photoreceptor thus obtained uses the PC copolymer of this embodiment, and therefore can prevent the coating liquid from becoming cloudy during the preparation of the photosensitive layer, and can also prevent gelation. In addition, since the photosensitive layer contains the PC copolymer of this embodiment as a binder resin, the photoreceptor has excellent durability (abrasion resistance) and excellent electrical properties (charging properties), and maintains excellent electrophotographic properties for a long period of time, and is suitable for use in various electrophotographic fields, such as copiers (monochrome, multicolor, full-color; analog, digital), printers (laser, LED, liquid crystal shutter), facsimiles, plate-making machines, and devices having multiple functions thereof.

[0176] In addition, when using the electrophotographic photoreceptor of this embodiment, corona discharge (corotron, scorotron), contact charging (charging roll, charging brush), etc. are used for charging. Examples of charging methods include a DC charging method and an AC / DC superimposed charging method in which AC is superimposed. In addition, any of a halogen lamp, a fluorescent lamp, a laser (semiconductor, He-Ne), an LED, and a photoreceptor internal exposure method may be used for exposure. In development, a dry development method or a wet development method such as cascade development, two-component magnetic brush development, one-component insulating toner development, one-component conductive toner development, etc. are used. In transfer, for example, an electrostatic transfer method (for example, corona transfer, roller transfer, belt transfer, etc.), a pressure transfer method, and an adhesive transfer method are used. In fixation, for example, a heat roller fixation, a radiant flash fixation, an open fixation, and a pressure fixation are used. In addition, in cleaning and destaticization, for example, a brush cleaner, a magnetic brush cleaner, an electrostatic brush cleaner, a magnetic roller cleaner, and a blade cleaner are used. In addition, a cleanerless method may be adopted. As the resin for the toner, for example, styrene resin, styrene-acrylic copolymer resin, polyester, epoxy resin, and cyclic hydrocarbon polymer can be used. The shape of the toner may be spherical or irregular. Toner controlled to a certain shape (for example, spheroidal or potato-shaped) can also be used. The toner may be any of pulverized toner, suspension polymerized toner, emulsion polymerized toner, chemically granulated toner, and ester elongation toner.

[0177] [Electrical equipment configuration] The electrical device of the present embodiment has the electrophotographic photoreceptor of the present embodiment (for example, a photoreceptor drum using the electrophotographic photoreceptor of the present embodiment, etc.) Examples of such electrical devices include copiers and printers such as laser printers. Since the electrical device of the present embodiment has the electrophotographic photoreceptor of the present embodiment, which has excellent abrasion resistance, the frequency of replacing the photoreceptor drum and the like is reduced, which is a great cost advantage.

[0178] [Modifications of the embodiment] The present invention is not limited to the above-described embodiment, and any modifications and improvements that can achieve the object of the present invention are included in the present invention. EXAMPLES

[0179] Next, the present invention will be described in more detail with reference to examples and comparative examples. However, the present invention is not limited to these examples, and various modifications and applications are possible without departing from the spirit of the present invention.

[0180] [Production Example: Preparation of Oligomers] <Production Example 1: Synthesis of bisphenol Z oligomer (bischloroformate)> 56.6 kg (224 mol) of 1,1-bis(4-hydroxyphenyl)cyclohexane (bisphenol Z) was suspended in 1080 L of methylene chloride, and 66.0 kg (667 mol) of phosgene was added thereto to dissolve it. A solution of 44.0 kg (435 mol) of triethylamine dissolved in 120 L of methylene chloride was added dropwise to the suspension at 2.2°C to 17.8°C over 2 hours and 50 minutes. After stirring for 30 minutes at 17.9°C to 19.6°C, 900 L of methylene chloride was distilled off at 14°C to 20°C. The remaining liquid was washed with 210 L of pure water, 1.2 kg of concentrated hydrochloric acid, and 450 g of hydrosulfite. After that, washing was repeated five times with 210 L of pure water to obtain a methylene chloride solution of bisphenol Z oligomer having a chloroformate group at the molecular end. The chloroformate concentration of the obtained solution was 1.14 mol / L, the solid concentration was 0.22 kg / L, and the average number of monomers was 1.02. Hereinafter, the raw material obtained in Production Example 1 is referred to as Z-CF. The raw material Z-CF is a bischloroformate oligomer represented by the general formula (2A).

[0181] The average number of monomers (n2) was calculated using the following formula. Average number of molecules (n2)=1+(Mav-M1) / M2 (Math 1) (In formula (Math. 1), Mav is (2×1000 / (CF value)), M2 is (M1-98.92), M1 is the molecular weight of the bischloroformate compound when n2=1 in general formula (2A), the CF value (N / kg) is (CF value / concentration), the CF value (N) is the number of chlorine atoms in the bischloroformate compound represented by general formula (2A) contained in 1 L of reaction solution, and the concentration (kg / L) is the amount of solids obtained by concentrating 1 L of reaction solution. Here, 98.92 is the total atomic weight of two chlorine atoms, one oxygen atom, and one carbon atom that are eliminated by polycondensation between bischloroformate compounds.)

[0182] <Production Example 2: Synthesis of bisphenol CZ oligomer (bischloroformate)> A solution of 199.4g (1.97mol) of triethylamine diluted with 460mL of methylene chloride was added dropwise to a mixture of 266g (0.897mol) of 1,1-bis(3-methyl-4-hydroxyphenyl)cyclohexane (bisphenol CZ), 1058mL of methylene chloride, and 187g (1.89mol) of phosgene at 13℃ to 16℃ over 3 hours and 6 minutes. The reaction mixture was stirred at 14℃ to 16℃ for 1 hour and 38 minutes. The reaction mixture was washed with 5.0mL of concentrated hydrochloric acid and 200mL of pure water. After that, washing with water was repeated until the aqueous layer became neutral, and a methylene chloride solution of bisphenol C oligomer having a chloroformate group at the molecular end was obtained. The chloroformate concentration of the obtained solution was 1.01 mol / L, the solid concentration was 0.22 kg / L, and the average number of monomers was 1.10. Hereinafter, the raw material obtained in Production Example 2 is referred to as CZ-CF. The raw material CZ-CF is a bischloroformate oligomer represented by the general formula (2A).

[0183] <Production Example 3: Synthesis of m-terphenyl oligomer (bischloroformate)> 250g (0.862 mol) of 4,4"-dihydroxy-m-terphenyl was suspended in 1000mL of methylene chloride, and 179g (1.81 mol) of phosgene was added thereto to dissolve it. A solution of 183.2g (1.82 mol) of triethylamine dissolved in 500mL of methylene chloride was added dropwise to this at 13℃ to 17℃ over 2 hours and 50 minutes. After stirring for 30 minutes at 14℃ to 16℃, 850mL of methylene chloride was distilled off at 14℃ to 20℃. The remaining liquid was washed with 210mL of pure water and 5.0mL of concentrated hydrochloric acid. Thereafter, washing with water was repeated until the aqueous layer became neutral, and a methylene chloride solution of bisphenol Z oligomer having a chloroformate group at the molecular end was obtained. The chloroformate concentration of the obtained solution was 1.14 mol / L, the solid concentration was 0.17 kg / L, and the average number of monomers was 1.03. Hereinafter, the raw material obtained in Production Example 3 is referred to as mT-CF. The raw material mT-CF is a bischloroformate oligomer represented by the general formula (1A).

[0184] The average number of monomers (n1) was determined in the same manner as the average number of monomers (n2) described above.

[0185] <Production Example 4: Synthesis of bisphenol B oligomer (bischloroformate)> A solution of 200.8g (1.98mol) of triethylamine diluted with 460mL of methylene chloride was added dropwise to a mixture of 210g (0.867mol) of 2,2-bis(4-hydroxyphenyl)butane (bisphenol B), 1058mL of methylene chloride, and 183g (1.85mol) of phosgene at 14℃ to 18.5℃ over 2 hours and 50 minutes. The reaction mixture was stirred at 18.5℃ to 19℃ for 1 hour, and then 600mL of methylene chloride was distilled off at 10℃ to 22℃. The reaction mixture was washed with 15.0mL of concentrated hydrochloric acid, 150mL of pure water, and 0.100g of hydrosulfite. After that, washing with water was repeated until the aqueous layer became neutral, and a methylene chloride solution of bisphenol B oligomer having a chloroformate group at the molecular end was obtained. The same procedure as in Production Example 1 was carried out except that the diluted solution was added dropwise, to obtain a methylene chloride solution of bisphenol B oligomer having chloroformate groups at the molecular terminals. The chloroformate concentration of the obtained solution was 1.16 mol / L, the solid concentration was 0.24 kg / L, and the average number of monomers was 1.08. Hereinafter, the raw material obtained in Production Example 4 is referred to as B-CF. The raw material B-CF is a bischloroformate oligomer represented by the general formula (2A).

[0186] <Production Example 5: Synthesis of PC oligomer of bisphenol Z> 120.0 g (0.448 mol) of 1,1-bis(4-hydroxyphenyl)cyclohexane (bisphenol Z) was added to an alkaline solution prepared by dissolving 46 g (1.15 mol) of sodium hydroxide and 64 g (1.14 mol) of potassium hydroxide in 1.24 L of pure water. 0.64 L of methylene chloride was added and stirred. While cooling to 5°C, 69 g of phosgene gas was blown into the liquid at a rate of 15 g / hr until the pH reached 9 or less. Next, after stopping the introduction of phosgene gas, the atmosphere was replaced with nitrogen and the reaction liquid was adjusted with hydrochloric acid to pH 7 to pH 9. This reaction liquid was allowed to stand and separated to obtain a methylene chloride solution of an oligomer having a chloroformate group at the molecular end. The chloroformate concentration of the obtained solution was 0.52 mol / L, the solid concentration was 0.220 kg / L, and the average number of polymerizations was 2.70. Hereinafter, the raw material obtained in Production Example 5 is referred to as PCOCH.

[0187] Example 1 (Production of PC copolymer) Into a reaction vessel equipped with a mechanical stirrer, stirring blades, and baffles, the raw material Z-CF (bischloroformate oligomer, average number of polymerizations: 1.02) (155 mL) obtained in Production Example 1 and methylene chloride (332 mL) were poured. To this, p-tert-butylphenol (0.119 g) was added as an end-capping agent, and the mixture was stirred so as to be thoroughly mixed. After cooling to a temperature inside the reactor of 15°C, the entire amount of the prepared 4,4"-dihydroxy-m-terphenyl solution (solution preparation method: 122 mL of 2.1 N potassium hydroxide aqueous solution (16.6 g of potassium hydroxide) was prepared, cooled to room temperature (25°C) or lower, 0.16 g of hydrosulfite was added as an antioxidant, and 18.5 g of 4,4"-dihydroxy-m-terphenyl was further added and completely dissolved) was added to this solution, and 1.8 mL of a triethylamine aqueous solution (7 vol%) was added while stirring, and stirring was continued for 1 hour. The resulting reaction mixture was diluted with 0.36 L of methylene chloride and 0.03 L of water, and washed. The lower layer was separated and further washed once with 0.15 L of water, once with 0.15 L of 0.03 N hydrochloric acid, and three times with 0.15 L of water, in that order. The resulting methylene chloride solution was dropped into warm water at 60°C to 70°C while stirring, and the resulting precipitate was filtered and dried to obtain a PC copolymer (PC-1) having the following structure.

[0188] (Specification of PC copolymer) The PC copolymer (PC-1) thus obtained was dissolved in methylene chloride to prepare a solution with a concentration of 0.5 g / dL. The reduced viscosity at 20°C [η SP The viscosity of the resulting PC copolymer (PC-1) was 1.22 dL / g. 1 H-NMR spectrum and 13 Analysis by C-NMR spectrum confirmed that the polymer was a PC copolymer having the following repeating units and composition: The reduced viscosity was measured using an automatic viscosity measuring device VMR-042 manufactured by Rigo Co., Ltd., and an improved Ubbelohde viscometer for automatic viscosity (RM type). 1 H-NMR spectrum and 13The measurement conditions for C-NMR spectrum are as follows.

[0189] ( 1 H-NMR spectrum measurement conditions) Equipment: JEOL Ltd. (JNM-ECZ400S) Solvent: CD2Cl2 Measurement concentration (sample volume / solvent volume): 1.5mg / mL Number of times: 64 (approx. 3 min)

[0190] ( 13 C-NMR spectrum measurement conditions) Equipment: Bruker Japan Co., Ltd. (AVANCE III HD 500) (5mmφ TCI cryoprobe used) Solvent: CD2Cl2 Measurement concentration (sample volume / solvent volume): 50mg / mL -Number of times of accumulation: 1024 times (about 1 hour)

[0191] [ka]

[0192] [ka]

[0193] a=Ar 1 / (Ar 1 +Ar 2 ) = 0.45 b=Ar 2 / (Ar 1 +Ar 2 ) = 0.55

[0194] The structure of the general formula (PC-1) was confirmed by the following procedure. first, 1 H-NMR spectrum and 13Using the C-NMR spectrum, an assignment analysis was performed, and the molar copolymerization ratio a in the repeating unit A and the molar copolymerization ratio b in the repeating unit B were calculated from the integrated intensity according to the following formula. a=Ar 1 / (Ar 1 +Ar 2 )…(Math A) b=Ar 2 / (Ar 1 +Ar 2 )…(Number B)

[0195] (Production of coating fluid and electrophotographic photoreceptor) An electrophotographic photoreceptor was manufactured by using a polyethylene terephthalate (PET) resin film with aluminum metal vapor deposition as a conductive substrate, and sequentially laminating a charge generating layer and a charge transport layer on the surface of the film to form a laminated photosensitive layer. 0.5 parts by mass of oxotitanium phthalocyanine was used as the charge generating material, and 0.5 parts by mass of butyral resin was used as the binder resin. These were added to 19 parts by mass of methylene chloride as a solvent, dispersed in a ball mill, and the dispersion was applied to the surface of the conductive substrate film with a bar coater and dried to form a charge generating layer having a thickness of about 0.5 μm. Next, 0.5 g of the compound (CTM-1) represented by the following formula (23) as a charge transport material and 0.5 g of the PC copolymer (PC-1) obtained in the above example were dispersed in 10 mL of tetrahydrofuran to prepare a coating liquid, which was then applied onto the charge generation layer with an applicator and dried to form a charge transport layer with a thickness of about 20 μm.

[0196] [ka]

[0197] [Evaluation of PC copolymer and electrophotographic photoreceptor] (Solubility of PC copolymer) The solubility of the PC copolymer was evaluated by adding the PC copolymer (PC-1) (1 g) obtained above to THF (9 g), stirring with a shaker for 30 minutes, and visually observing the insoluble parts in the liquid and the degree of turbidity. When the PC copolymer (PC-1) was dissolved and no turbidity was observed, it was rated as "dissolved," when there was an insoluble part, it was rated as "insoluble," and when it became turbid, it was rated as "turbid."

[0198] (Transparency of PC copolymer (HAZE value)) The haze value (%) was measured using the solution used in the evaluation of the solubility of the PC copolymer (a THF solution containing 10% by mass of solid content of PC-1). The haze value (%) was measured in accordance with JISK 7136 (2000). A haze meter (NDH500) manufactured by Nippon Denshoku Industries Co., Ltd. was used as the measuring device. The international standard number corresponding to JISK 7136 is ISO 14782 (1999). The haze value (%) can also be measured in accordance with ISO 14782 (1999).

[0199] (Tensile properties (breaking strain) of PC copolymer) PC copolymer (PC-1) (2.5 g) was added to methylene chloride (20 mL) and stirred for 60 minutes with a shaker, after which the solution was spread in a petri dish with a diameter of 150 mm. It was then air-dried for one day and further dried in a dryer at 100°C for 10 hours. A film sample of 40 mm x 6 mm (2 mm necked part) x approximately 90 μm thick was prepared from the dried sample using a punching tool for tensile testing. The breaking strain (%) of the PC copolymer (PC-1) was measured using this film sample. The breaking strain (%) was measured using a benchtop tensile tester (EZgraph, manufactured by Shimadzu Corporation) at a tension speed of 1 mm / min.

[0200] (Abrasion resistance of PC copolymer and electrophotographic photoreceptor) [Preparation 1] Preparation of copolymer sample for evaluating wear resistance PC copolymer (PC-1) (2 g) was dissolved in methylene chloride (12 mL) and cast onto a commercially available PET film using an applicator. The film was heated under reduced pressure (100 Pa or less) to remove the solvent, and a film sample of 100 mm x 100 mm x approximately 30 μm thick was obtained.

[0201] [Preparation 2] Preparation of a sample for evaluating the wear resistance of the photoreceptor PC copolymer (PC-1) (1 g) and CTM-1 (0.67 g) were dissolved in THF (10 mL) and cast onto a commercially available PET film using an applicator. The film was heated under reduced pressure (100 Pa or less) to remove the solvent, and a film sample of 100 mm x 100 mm x approximately 30 μm thick was obtained.

[0202] [Evaluation of wear resistance] The abrasion resistance of the cast surfaces of the films prepared in the above [Preparation 1] and [Preparation 2] was evaluated. The wear resistance was evaluated in an abrasive wear mode using a Taber wear tester (manufactured by Toyo Seiki Seisakusho, Ltd.). The test conditions were as follows: an abrasive wheel (model number: CS-10) with a load of 500 g was brought into contact with the film surface, and the mass loss (mg) was measured after 700 rotations in the case of [Preparation 1], and after 300 rotations in the case of [Preparation 2].

[0203] (Charging characteristics of electrophotographic photoreceptor) Next, the electrophotographic characteristics of the electrophotographic photoreceptor manufactured as described above were measured using a static charge tester CYNTHIA54IM (manufactured by Gentec Co., Ltd.). Under the conditions of EV (exposure sensitivity measurement) mode and initial charge amount of -700V, the initial surface potential V0 (V) and the residual potential after 5 seconds of light irradiation (10 Lux) (initial residual potential V R (V) was measured.

[0204] The results of these evaluations are shown in Table 1. For Examples 2 to 5 and Comparative Examples 1 to 3 described later, evaluation samples of the copolymers and photoreceptors were prepared using the PC copolymers obtained in each example instead of the PC copolymer (PC-1), and similar evaluations were performed. The results are also shown in Table 1.

[0205] Example 2 (Production of PC copolymer) Into a reaction vessel equipped with a mechanical stirrer, stirring blades, and baffles, the raw material CZ-CF (bischloroformate oligomer, average polymerization number 1.10) (155 mL) obtained in Production Example 2 and methylene chloride (332 mL) were poured. To this was added p-tert-butylphenol (0.143 g) as an end-capping agent, and the mixture was stirred until thoroughly mixed. After cooling the temperature inside the reactor to 15°C, the entire amount of the prepared 4,4"-dihydroxy-m-terphenyl solution (solution preparation method: 122mL of 1.85N potassium hydroxide aqueous solution (14.7g of potassium hydroxide) was prepared, cooled to room temperature (25°C) or lower, 0.14g of hydrosulfite was added as an antioxidant, and 16.4g of 4,4"-dihydroxy-m-terphenyl was further added and completely dissolved) was added to this solution, and 1.6mL of an aqueous triethylamine solution (7vol%) was added with stirring, and stirring was continued for 80 minutes. The resulting reaction mixture was diluted with 0.36 L of methylene chloride and 0.03 L of water, and washed. The lower layer was separated and further washed once with 0.15 L of water, once with 0.15 L of 0.03 N hydrochloric acid, and three times with 0.15 L of water, in that order. The resulting methylene chloride solution was dropped into warm water at 60°C to 70°C while stirring, and the resulting precipitate was filtered and dried to obtain a PC copolymer (PC-2) having the following structure. Reduced viscosity [η of PC copolymer (PC-2) at 20℃ SP / C] was 1.21 dL / g, and the structure was confirmed by NMR to be a PC copolymer consisting of the following repeating units and composition:

[0206] [ka]

[0207] [ka]

[0208] a=Ar 1 / (Ar 1 +Ar 2 ) = 0.40 b=Ar 2 / (Ar 1 +Ar 2 ) = 0.60

[0209] Example 3 Into a reaction vessel equipped with a mechanical stirrer, stirring blades, and baffles, the raw material Z-CF (bischloroformate oligomer, average molecular weight: 1.02) (155 mL) obtained in Production Example 1 and methylene chloride (332 mL) were poured. To this was added p-tert-butylphenol (0.119 g) as an end-capping agent, and the mixture was stirred until thoroughly mixed. After cooling the temperature inside the reactor to 15°C, the entire amount of the 3,3''-dimethyl-4,4''-dihydroxy-m-terphenyl solution (solution preparation method: 122mL of 2.1N potassium hydroxide aqueous solution (16.6g of potassium hydroxide) was prepared, cooled to room temperature (25°C) or lower, 0.14g of hydrosulfite was added as an antioxidant, and 20.5g of 3,3''-dimethyl-4,4''-dihydroxy-m-terphenyl was further added and completely dissolved) was added to this solution, and 2.0mL of a triethylamine aqueous solution (7vol%) was added with stirring, and stirring was continued for 1 hour. The resulting reaction mixture was diluted with 0.36 L of methylene chloride and 0.03 L of water, and washed. The lower layer was separated and further washed once with 0.15 L of water, once with 0.15 L of 0.03 N hydrochloric acid, and three times with 0.15 L of water, in that order. The resulting methylene chloride solution was dropped into warm water at 60°C to 70°C while stirring, and the resulting precipitate was filtered and dried to obtain a PC copolymer (PC-3) having the following structure. Reduced viscosity [η of PC copolymer (PC-3) at 20℃ SP / C] was 1.15 dL / g, and the structure was confirmed by NMR to be a PC copolymer consisting of the following repeating units and composition:

[0210] [ka]

[0211] [ka]

[0212] a=Ar 1 / (Ar 1 +Ar 2 ) = 0.42 b=Ar 2 / (Ar 1 +Ar 2 ) = 0.58

[0213] Example 4 In a reaction vessel equipped with a mechanical stirrer, stirring blades, and baffles, the raw material mT-CF (bischloroformate oligomer, average number of monomers: 1.03) (145 mL) obtained in Production Example 3 and methylene chloride (208 mL) were poured. p-tert-butylphenol (0.234 g) was added as an end-capping agent and stirred to mix thoroughly. After cooling to a temperature of 15°C inside the reactor, the entire amount of the prepared bisphenol Z solution (solution preparation method: 88 mL of 2.7 N potassium hydroxide aqueous solution (15.6 g of potassium hydroxide) was prepared, cooled to room temperature (25°C) or lower, 0.16 g of hydrosulfite was added as an antioxidant, and 17.8 g of bisphenol Z was added and completely dissolved) was added to this solution, and 1.7 mL of triethylamine aqueous solution (7 vol%) was added while stirring, and stirring was continued for 80 minutes. The resulting reaction mixture was diluted with 0.3 L of methylene chloride and 0.03 L of water, and washed. The lower layer was separated and further washed once with 0.1 L of water, once with 0.1 L of 0.03 N hydrochloric acid, and three times with 0.1 L of water, in that order. The resulting methylene chloride solution was dropped into warm water at 60°C to 70°C while stirring, and the resulting reprecipitate was filtered and dried to obtain a PC copolymer (PC-4) having the following structure. Reduced viscosity [η of PC copolymer (PC-4) at 20℃ SP / C] was 1.15 dL / g, and the structure was confirmed by NMR to be a PC copolymer consisting of the following repeating units and composition:

[0214] [ka]

[0215] [ka]

[0216] a=Ar 1 / (Ar 1 +Ar 2 ) = 0.52 b=Ar 2 / (Ar 1 +Ar 2 ) = 0.48

[0217] Example 5 Into a reaction vessel equipped with a mechanical stirrer, stirring blades, and baffles, the raw material B-CF (bischloroformate oligomer, average number of polymerizations: 1.08) (150 mL) obtained in Production Example 4 and methylene chloride (364 mL) were poured. To this, p-tert-butylphenol (0.130 g) was added as an end-capping agent, and the mixture was stirred so as to be thoroughly mixed. After cooling to a temperature inside the reactor of 10°C, the entire amount of the 4,4"-dihydroxy-m-terphenyl solution (solution preparation method: 129 mL of 2.0 N potassium hydroxide aqueous solution (18.3 g of potassium hydroxide) was prepared, cooled to room temperature (25°C) or lower, 0.25 g of hydrosulfite was added as an antioxidant, and 18.3 g of 4,4"-dihydroxy-m-terphenyl was further added and completely dissolved) was added to this solution, and 1.8 mL of a triethylamine aqueous solution (7 vol%) was added while stirring, and stirring was continued for 80 minutes. The resulting reaction mixture was diluted with 0.33 L of methylene chloride and 0.02 L of water, and washed. The lower layer was separated and further washed once with 0.15 L of water, once with 0.15 L of 0.30 N hydrochloric acid, and three times with 0.15 L of water, in that order. The resulting methylene chloride solution was dropped into warm water at 60°C to 70°C while stirring, and the resulting reprecipitate was filtered and dried to obtain a PC copolymer (PC-5) having the following structure. Reduced viscosity [η of PC copolymer (PC-5) at 20℃ SP / C] was 1.20 dL / g, and the structure was confirmed by NMR to be a PC copolymer consisting of the following repeating units and composition:

[0218] [ka]

[0219] [ka]

[0220] a=Ar 1 / (Ar 1 +Ar 2 ) = 0.38 b=Ar 2 / (Ar 1 +Ar 2 ) = 0.62

[0221] Comparative Example 1 Into a reaction vessel equipped with a mechanical stirrer, stirring blades, and baffles, the raw material Z-CF (bischloroformate oligomer, average number of polymerizations: 1.02) (155 mL) obtained in Production Example 1 and methylene chloride (332 mL) were poured. To this, p-tert-butylphenol (0.317 g) was added as an end-capping agent, and the mixture was stirred so as to be thoroughly mixed. After cooling to a temperature inside the reactor of 15°C, the entire amount of the 4,4"-dihydroxy-p-terphenyl solution (solution preparation method: 122 mL of 2.1 N potassium hydroxide aqueous solution (16.6 g of potassium hydroxide) was prepared, cooled to room temperature (25°C) or lower, 0.16 g of hydrosulfite was added as an antioxidant, and 18.5 g of 4,4"-dihydroxy-p-terphenyl was further added and completely dissolved) was added to this solution, and 1.8 mL of a triethylamine aqueous solution (7 vol%) was added while stirring, and stirring was continued for 80 minutes. The resulting reaction mixture was diluted with 0.36 L of methylene chloride and 0.03 L of water, and washed. The lower layer was separated and further washed once with 0.15 L of water, once with 0.15 L of 0.03 N hydrochloric acid, and three times with 0.15 L of water, in that order. The resulting methylene chloride solution was dropped into warm water at 60°C to 70°C while stirring, and the resulting reprecipitate was filtered and dried to obtain a PC copolymer (PC-6) having the following structure. Reduced viscosity [η of PC copolymer (PC-6) at 20℃ SP / C] was 1.17 dL / g, and the structure was confirmed by NMR to be a PC copolymer consisting of the following repeating units and composition:

[0222] [ka]

[0223] [ka]

[0224] a=Ar 1 / (Ar 1 +Ar 2 ) = 0.42 b=Ar 2 / (Ar 1 +Ar 2 ) = 0.58

[0225] Comparative Example 2 Into a reaction vessel equipped with a mechanical stirrer, stirring blades, and baffles, the raw material PCOCH (bischloroformate oligomer, average number of polymerizations: 2.70) (155 mL) obtained in Production Example 5 and methylene chloride (332 mL) were poured. To this, p-tert-butylphenol (0.161 g) was added as an end-capping agent, and the mixture was stirred so as to be thoroughly mixed. After cooling to a temperature inside the reactor of 15°C, the entire amount of the 4,4"-dihydroxy-m-terphenyl solution (solution preparation method: 122 mL of 1.0 N potassium hydroxide aqueous solution (7.6 g of potassium hydroxide) was prepared, cooled to room temperature (25°C) or lower, 0.08 g of hydrosulfite was added as an antioxidant, and 8.46 g of 4,4"-dihydroxy-m-terphenyl was further added and completely dissolved) was added to this solution, and 0.8 mL of a triethylamine aqueous solution (7 vol%) was added while stirring, and stirring was continued for 1 hour. The resulting reaction mixture was diluted with 0.36 L of methylene chloride and 0.03 L of water, and washed. The lower layer was separated and further washed once with 0.15 L of water, once with 0.15 L of 0.03 N hydrochloric acid, and three times with 0.15 L of water, in that order. The resulting methylene chloride solution was dropped into warm water at 60°C to 70°C while stirring, and the resulting reprecipitate was filtered and dried to obtain a PC copolymer (PC-7) having the following structure. Reduced viscosity [η of PC copolymer (PC-7) at 20℃ SP / C] was 1.19 dL / g, and the structure was confirmed by NMR to be a PC copolymer consisting of the following repeating units and composition:

[0226] [ka]

[0227] [ka]

[0228] a=Ar 1 / (Ar 1 +Ar 2 ) = 0.15 b=Ar2 / (Ar 1 +Ar 2 ) = 0.85

[0229] Comparative Example 3 Into a reaction vessel equipped with a mechanical stirrer, stirring blades, and baffles, the raw material Z-CF (bischloroformate oligomer, average number of polymerizations: 1.02) (155 mL) obtained in Production Example 1 and methylene chloride (332 mL) were poured. To this, p-tert-butylphenol (0.293 g) was added as an end-capping agent, and the mixture was stirred so as to be thoroughly mixed. After cooling to a temperature inside the reactor of 15°C, the entire amount of the 4,4"-biphenol solution (solution preparation method: 122 mL of 2.1 N potassium hydroxide aqueous solution (16.6 g of potassium hydroxide) was prepared, cooled to room temperature (25°C) or lower, 0.12 g of hydrosulfite was added as an antioxidant, and 13.16 g of 4,4"-biphenol was further added and completely dissolved) was added to this solution, and 1.8 mL of a triethylamine aqueous solution (7 vol%) was added while stirring, and stirring was continued for 1 hour. The resulting reaction mixture was diluted with 0.36 L of methylene chloride and 0.03 L of water, and washed. The lower layer was separated and further washed once with 0.15 L of water, once with 0.15 L of 0.03 N hydrochloric acid, and three times with 0.15 L of water, in that order. The resulting methylene chloride solution was dropped into warm water at 60°C to 70°C while stirring, and the resulting reprecipitate was filtered and dried to obtain a PC copolymer (PC-8) having the following structure. Reduced viscosity [η of PC copolymer (PC-8) at 20℃ SP / C] was 1.21 dL / g, and the structure was confirmed by NMR to be a PC copolymer consisting of the following repeating units and composition:

[0230] [ka]

[0231] [Table 1]

[0232] [Evaluation results] Table 1 shows the evaluation results of Examples 1 to 5 and Comparative Examples 1 to 3. Comparing Examples 1 to 5 with Comparative Examples 1 to 3, it was confirmed that the PC copolymers of Examples 1 to 5 had good abrasion resistance and stable solubility in organic solvents. Furthermore, the PC copolymers of Examples 1 to 5 had good breaking strain and excellent transparency. For example, in Example 1, a low-molecular oligomer having a divalent aromatic group of bisphenol Z (raw material Z-CF) was reacted with 4,4"-dihydroxy-m-terphenyl monomer by the production method described herein to obtain a PC copolymer (PC-1) having a copolymerization ratio (mol %) of repeating unit B derived from bisphenol Z to repeating unit A derived from 4,4"-dihydroxy-m-terphenyl of repeating unit B: repeating unit A = 55:45. The reduced viscosity was also 1.22 [dL / g]. The PC copolymer (PC-1) of Example 1 has good abrasion resistance and good wear-related breaking strain, as shown in the evaluation results, even when compared with a polycarbonate copolymer obtained by reacting a low-mer bischloroformate oligomer having a divalent aromatic group of bisphenol Z with a biphenol monomer (e.g., Example 10 of JP-A-2011-26574). Furthermore, despite containing a relatively high proportion of rigid terphenyl skeletons, the PC copolymer (PC-1) of Example 1 has excellent solubility in organic solvents, can suppress the clouding of the solution due to crystallization, and has good abrasion resistance and electrophotographic properties even in electrophotographic photoreceptor applications. The PC copolymer of Comparative Example 1 was confirmed to have good abrasion resistance, as in Examples 1 to 5, but had poor solubility in THF and was almost insoluble. The PC copolymers of Comparative Examples 2 to 3 had poor abrasion resistance compared to Examples 1 to 5, and were found to have insufficient abrasion resistance for use in recent high-durability machines. In Comparative Examples 2 to 3, the influence of the PC copolymer evaluation also appeared in the photoreceptor evaluation, and the abrasion resistance of the photoreceptor deteriorated. From the above, it was found that the PC copolymers of Examples 1 to 5 have high abrasion resistance, good breaking strain, and excellent solubility in organic solvents. Furthermore, Examples 1 to 5 also showed good results in terms of abrasion resistance and electrical properties in the photoreceptor evaluation. [Industrial Applicability]

[0233] The polycarbonate copolymer of the present invention can be suitably used as a binder resin for a photosensitive layer of an electrophotographic photoreceptor. In addition, a photoreceptor drum made using the electrophotographic photoreceptor of the present invention can be suitably used in electric devices such as copying machines and printers such as laser printers.

Claims

1. A polycarbonate copolymer, The polycarbonate copolymer has a repeating unit A represented by the following general formula (1) and a repeating unit B represented by the following general formula (2), and is obtained from at least one of a bischloroformate oligomer represented by the following general formula (1A) and a bischloroformate oligomer represented by the following general formula (2A), The average number of monomers of the bischloroformate oligomer represented by the general formula (1A), n 1 is 1.0 or more and 1.3 or less, The average number of monomers of the bischloroformate oligomer represented by the general formula (2A), n 2 is 1.0 or more and 1.3 or less, Polycarbonate copolymer. 【Chemistry 1】 (In the above general formula (1), Ar 1 is a group represented by the following general formula (3): In the general formula (2), Ar 2 is a group represented by the following general formula (4): However, the group represented by the following general formula (4) is A divalent group obtained by removing two hydroxy groups from bisphenol A, A divalent group obtained by removing two hydroxy groups from 1,1-bis(4-hydroxyphenyl)ethane, A divalent group obtained by removing two hydroxy groups from 1,1-bis(4-hydroxyphenyl)propane, A divalent group obtained by removing two hydroxy groups from 2,2-bis(4-hydroxyphenyl)pentane, and It is not any of the divalent groups obtained by removing two hydroxy groups from 3,3-bis(4-hydroxyphenyl)pentane. 【Chemistry 2】 [In the general formulas (3) and (4), R 11 ~R 18 and R 21 ~R 28 are each independently a hydrogen atom or a substituent, R as a Substituent 11 ~R 18 and R 21 ~R 28 are each independently an unsubstituted alkyl group having 1 to 2 carbon atoms; an unsubstituted fluoroalkyl group having 1 to 2 carbon atoms; an unsubstituted alkoxy group having 1 to 2 carbon atoms, X 1 teeth, -CR 3 R 4 A group represented by -, a substituted or unsubstituted cycloalkylidene group having 5 to 6 carbon atoms, a substituted or unsubstituted bicyclohydrocarbon diyl group having 7 to 10 carbon atoms, or a substituted or unsubstituted tricyclohydrocarbon diyl group having 10 to 16 carbon atoms, R 3 and R 4 are each independently a hydrogen atom or a substituent, R as a Substituent 3 and R 4 are each independently an unsubstituted alkyl group having 1 to 3 carbon atoms; an unsubstituted fluoroalkyl group having 1 to 3 carbon atoms, or It is a substituted or unsubstituted aryl group having 6 to 12 ring carbon atoms.] 【Chemistry 3】 [In the above general formula (1A), Ar 1 is a group represented by the general formula (3), n 1 represents the average number of mers, In the general formula (2A), Ar 2 is a group represented by the general formula (4), n 2 represents the average number of monomers.

2. The polycarbonate copolymer according to claim 1, Ar 1 / (Ar 1 +Ar 2 ) is 30 mol % or more and 55 mol % or less, Ar 2 / (Ar 1 +Ar 2 ) is 45 mol% or more and 70 mol% or less; Polycarbonate copolymer.

3. The polycarbonate copolymer according to claim 1 or 2, In the general formula (4), X 1 teeth, -CR 3 R 4 A group represented by -, or a substituted or unsubstituted cycloalkylidene group having 5 to 6 carbon atoms, R 3 and R 4 are each independently An unsubstituted alkyl group having 1 to 3 carbon atoms. Polycarbonate copolymer.

4. The polycarbonate copolymer according to any one of claims 1 to 3, In the general formula (1), Ar 1 is a divalent group derived from 4,4″-dihydroxy-m-terphenyl, In the general formula (2), Ar 2 is a group represented by the following general formula (4A): Polycarbonate copolymer. 【Chemistry 4】 (In the general formula (4A), R 21 ~R 28 each independently represents R in the general formula (4). 21 ~R 28 (Same meaning as above.)

5. The polycarbonate copolymer according to any one of claims 1 to 3, In the general formula (2), Ar 2 is a group represented by the following general formula (4A) or (4B): Polycarbonate copolymer. 【Chemistry 5】 (In the general formulas (4A) and (4B), R 21 ~R 28 each independently represents R in the general formula (4). 21 ~R 28 (Same meaning as above.)

6. The polycarbonate copolymer according to any one of claims 1 to 5, R 11 ~R 18 and R 21 ~R 28 are each independently a hydrogen atom, or An unsubstituted alkyl group having 1 to 2 carbon atoms. Polycarbonate copolymer.

7. The polycarbonate copolymer according to any one of claims 1 to 6, The polycarbonate copolymer is dissolved in THF at a solid content concentration of 10% by mass, and the HAZE value of the solution is 3% or less. Polycarbonate copolymer.

8. The polycarbonate copolymer according to any one of claims 1 to 7, The polycarbonate copolymer has a breaking strain of 65% or more at a tensile speed of 1 mm / min in a tensile test. Polycarbonate copolymer.

9. The polycarbonate copolymer according to any one of claims 1 to 8, When the structural units AA, BB, AB, and BA each constituted by two consecutive repeating units A represented by the general formula (1) and two consecutive repeating units B represented by the general formula (2) are defined as a diad, The percentage of the number of moles of the diad represented by AA to the total number of moles of the four types of diads represented by AA, BB, AB, and BA is 5 mol % or less. Polycarbonate copolymer.

10. The polycarbonate copolymer according to any one of claims 1 to 8, When the structural units ABA, BAA, AAA, AAB, BBA, BAB, ABB, and BBB each constituted by three consecutive repeating units A represented by the general formula (1) and three consecutive repeating units B represented by the general formula (2) are defined as a triad, the percentage of the number of moles of the triad represented by AAA to the total number of moles of the total eight types of triads represented by ABA, BAA, AAA, AAB, BBA, BAB, ABB, and BBB is 3 mol % or less; Polycarbonate copolymer.

11. A method for producing a polycarbonate copolymer, comprising producing a polycarbonate copolymer by the following synthesis reaction (CS1), (CS2), or (CS3): (CS1) A bischloroformate oligomer represented by the following general formula (1A) and a dihydric phenolic compound represented by the following general formula (6) are subjected to interfacial polycondensation in the presence of an acid binder. (CS2) A bischloroformate oligomer represented by the following general formula (2A) and a dihydric phenolic compound represented by the following general formula (5) are subjected to interfacial polycondensation in the presence of an acid binder. (CS3) A bischloroformate oligomer represented by the following general formula (1A) is mixed with a bischloroformate oligomer represented by the following general formula (2A), and the mixture of the bischloroformate oligomer represented by the following general formula (1A) and the bischloroformate oligomer represented by the following general formula (2A) is subjected to interfacial polycondensation with a dihydric phenolic compound represented by the following general formula (5) or a dihydric phenolic compound represented by the following general formula (6). 【Chemistry 6】 [In the above general formulas (1A) and (5), Ar 1 is a group represented by the following general formula (3), and in the general formulas (2A) and (6), Ar 2 is a group represented by the following general formula (4): In the general formula (1A), n 1 represents the average number of monomers, which is 1.0 to 1.3, In the general formula (2A), n 2 represents the average number of monomers, which is 1.0 to 1.

3. 【Chemistry 7】 [In the general formulas (3) and (4), R 11 ~R 18 and R 21 ~R 28 are each independently a hydrogen atom or a substituent, R as a Substituent 11 ~R 18 and R 21 ~R 28 are each independently an unsubstituted alkyl group having 1 to 2 carbon atoms; an unsubstituted fluoroalkyl group having 1 to 2 carbon atoms; an unsubstituted alkoxy group having 1 to 2 carbon atoms, X 1 teeth, -CR 3 R 4 A group represented by -, a substituted or unsubstituted cycloalkylidene group having 5 to 6 carbon atoms, a substituted or unsubstituted bicyclohydrocarbon diyl group having 7 to 10 carbon atoms, or a substituted or unsubstituted tricyclohydrocarbon diyl group having 10 to 16 carbon atoms, R 3 and R 4 are each independently a hydrogen atom or a substituent, R as a Substituent 3 and R 4 are each independently an unsubstituted alkyl group having 1 to 3 carbon atoms; an unsubstituted fluoroalkyl group having 1 to 3 carbon atoms, or It is a substituted or unsubstituted aryl group having 6 to 12 ring carbon atoms.]

12. A coating liquid comprising the polycarbonate copolymer according to any one of claims 1 to 10 and an organic solvent.

13. An electrophotographic photoreceptor comprising the polycarbonate copolymer according to claim 1 .

14. A substrate; A photosensitive layer provided on the substrate, The photosensitive layer comprises the polycarbonate copolymer according to claim 1 .

15. An electric device comprising the electrophotographic photoreceptor according to claim 13 or 14.

Citation Information

Patent Citations

  • Electrophotographic sensitive body

    JP1992179961A

  • Electrophotographic photoreceptor and electrophotographic device with same

    JP1997043873A

  • Electrophotographic photoreceptor, electrophotographic device using the photoreceptor and device unit

    JP1997043882A

  • Printing ink

    JP2004315765A

  • Polycarbonate copolymer, coating liquid using the same, and electrophotographic photosensitive article

    JP2011026574A